Positive electrode composition, positive electrode, battery, method for producing coating liquid for forming positive electrode, method for producing positive electrode, and method for producing battery

By combining carbon black, carbon nanotubes and bonding materials, a positive electrode composition with excellent conductivity and dispersion was prepared, which solved the shortcomings of lithium-ion secondary batteries in terms of energy density, output characteristics and ambient temperature stability, and achieved the goal of achieving the Battery performance with small internal resistance and excellent cycle characteristics.

CN119256412APending Publication Date: 2025-01-03DENKA CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380042790.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-05-30
Filing Date
2023-03-29
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The positive electrode of the existing lithium-ion secondary battery has limitations in improving energy density and output characteristics, and is unstable to the ambient temperature and insufficient circulation characteristics.

Method used

Using a positive electrode composition composed of carbon black, carbon nanotubes and bonding materials, a coating solution with excellent conductivity and dispersion is prepared through specific aggregate proportions and shape distributions, combined with transmission electron microscopy analysis, to form a low viscosity slurry The composite material layer is formed by coating on the current collector.

Benefits of technology

The lithium-ion secondary battery has achieved small internal resistance, excellent discharge rate characteristics and cycle characteristics, and improved the stability and performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119256412A_ABST
    Figure CN119256412A_ABST
Patent Text Reader

Abstract

A positive electrode composition which contains carbon black, carbon nanotubes, a binder and an active material, and wherein: when the carbon black is divided into a first primary aggregate, a second primary aggregate, a third primary aggregate and a fourth primary aggregate, the ratio of the total number of the second primary aggregate and the third primary aggregate is 22% or more; the X value of the first primary aggregate is greater than 1.7, the Y value of the second primary aggregate is 1.2 or less, the Z value of the third primary aggregate is 2.0 or less, and the X value of the fourth primary aggregate is 1.7 or less, the Y value is greater than 1.2, and the Z value is greater than 2.0. In the formula, the Feret diameter in the short-axis direction of the primary aggregate is W ([mu] m), the Feret diameter in the long-axis direction is L ([mu] m), the circumference is P ([mu] m), and the projected area is A ([mu] m2). X = L / W (X), Y = P2 / 4pi A (Y), and Z = (L * W) / A (Z).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a positive electrode composition, a positive electrode, a battery, a method for producing a positive electrode-forming coating liquid, a method for producing a positive electrode, and a method for producing a battery. Background Art

[0002] As environmental and energy issues intensify, the development of technologies to reduce dependence on fossil fuels and realize a low-carbon society is being actively promoted. Such technological developments include the development of low-emission vehicles such as hybrid electric vehicles and electric vehicles, the development of natural energy power generation and storage systems such as solar power generation and wind power generation, and the development of a next-generation power transmission network that efficiently supplies electricity and reduces transmission losses.

[0003] One of the key devices that is common and necessary in these technologies is a battery. For such a battery, a high energy density is required in order to miniaturize the system. In addition, a high output characteristic is required in order to be able to provide a stable power supply without being affected by the ambient temperature of use. In addition, good cycle characteristics that can withstand long-term use are also required. Therefore, the replacement of the previous lead-acid batteries, nickel-cadmium batteries, and nickel-hydrogen batteries to lithium-ion secondary batteries with higher energy density, output characteristics, and cycle characteristics is being rapidly carried out.

[0004] In the past, the positive electrode of a lithium-ion secondary battery was manufactured by applying a positive electrode paste containing a positive electrode active material, a conductive material, and a binding material (also referred to as a binder) to a current collector. As the positive electrode active material, lithium-containing composite oxides such as lithium cobalt oxide and lithium manganese oxide are used. In addition, since the conductivity of the positive electrode active material is insufficient, a conductive material such as carbon black is added to the positive electrode paste for the purpose of imparting conductivity (for example, Patent Document 1).

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent Application Publication No. 2008-227481 Summary of the invention

[0008] Problems to be solved by the invention

[0009] In recent years, there has been a demand for further improvement in the performance of batteries such as lithium ion secondary batteries.

[0010] The object of the present invention is to provide a positive electrode composition for a battery having a small internal resistance and excellent discharge rate characteristics and cycle characteristics. In addition, the object of the present invention is to provide a method for manufacturing a coating liquid for forming a positive electrode of a battery having a small internal resistance and excellent discharge rate characteristics and cycle characteristics. In addition, the object of the present invention is to provide a positive electrode for a battery having a small internal resistance and excellent discharge rate characteristics and cycle characteristics and a method for manufacturing the same. In addition, the object of the present invention is to provide a battery having the above-mentioned positive electrode and a method for manufacturing the same.

[0011] Means for solving problems

[0012] The present invention relates to, for example, the following <1> ~ <7> .

[0013] <1> A positive electrode composition comprising carbon black, carbon nanotubes, a binder, and an active material,

[0014] The carbon nanotubes have an average diameter of 5 to 15 nm.

[0015] When the carbon black is divided into a first primary aggregate, a second primary aggregate, a third primary aggregate, and a fourth primary aggregate, the total number of the second primary aggregate and the third primary aggregate is 22% or more relative to the total number of the first primary aggregate, the second primary aggregate, the third primary aggregate, and the fourth primary aggregate,

[0016] The value of X of the first primary aggregate obtained by the following formula (X) is greater than 1.7,

[0017] The X value of the second primary aggregate is 1.7 or less, and the Y value obtained by the following formula (Y) is 1.2 or less,

[0018] The X value of the third primary aggregate is 1.7 or less, the Y value is greater than 1.2, and the Z value calculated by the following formula (Z) is 2.0 or less,

[0019] The fourth primary aggregate has the aforementioned X value of 1.7 or less, the aforementioned Y value of greater than 1.2, and the aforementioned Z value of greater than 2.0.

[0020] X=L / W (X)

[0021] Y=P 2 / 4πA (Y)

[0022] Z=(L×W) / A(Z)

[0023] [wherein, in the two-dimensional projection image of the primary aggregate obtained by transmission electron microscopy, the Fret diameter in the short axis direction of the primary aggregate is W (μm), the Fret diameter in the long axis direction of the primary aggregate is L (μm), the circumference of the primary aggregate is P (μm), and the projected area of ​​the primary aggregate is A (μm 2 ). ]

[0024] <2> like <1> The positive electrode composition, wherein the ratio of the average diameter of the carbon nanotubes to the BET specific surface area (average diameter / BET specific surface area) is 0.01 to 0.1 nm / (m 2 / g).

[0025] <3> The positive electrode comprises <1> or <2> The positive electrode composition forms a composite material layer.

[0026] <4> A battery having <3> The positive electrode.

[0027] <5> A method for producing a coating liquid for forming a positive electrode, comprising:

[0028] a mixing step of mixing carbon black with a first liquid medium to obtain a first agent containing the carbon black and the first liquid medium; and

[0029] a coating liquid forming step of mixing the first agent, the second agent containing carbon nanotubes and a second liquid medium, the third agent containing a binder and a third liquid medium, and the active material to form a positive electrode forming coating liquid,

[0030] The carbon nanotubes have an average diameter of 5 to 15 nm.

[0031] When the carbon black is divided into a first primary aggregate, a second primary aggregate, a third primary aggregate, and a fourth primary aggregate, the total number of the second primary aggregate and the third primary aggregate is 22% or more relative to the total number of the first primary aggregate, the second primary aggregate, the third primary aggregate, and the fourth primary aggregate,

[0032] The value of X of the first primary aggregate obtained by the following formula (X) is greater than 1.7,

[0033] The X value of the second primary aggregate is 1.7 or less, and the Y value obtained by the following formula (Y) is 1.2 or less,

[0034] The X value of the third primary aggregate is 1.7 or less, the Y value is greater than 1.2, and the Z value calculated by the following formula (Z) is 2.0 or less,

[0035] The fourth primary aggregate has the aforementioned X value of 1.7 or less, the aforementioned Y value of greater than 1.2, and the aforementioned Z value of greater than 2.0.

[0036] X=L / W (X)

[0037] Y=P 2 / 4πA (Y)

[0038] Z=(L×W) / A(Z)

[0039] [wherein, in the two-dimensional projection image of the primary aggregate obtained by transmission electron microscopy, the Fret diameter in the short axis direction of the primary aggregate is W (μm), the Fret diameter in the long axis direction of the primary aggregate is L (μm), the circumference of the primary aggregate is P (μm), and the projected area of ​​the primary aggregate is A (μm 2 ). ]

[0040] <6> The method for manufacturing a positive electrode comprises the following positive electrode forming step: <5> The coating liquid for forming the positive electrode manufactured by the manufacturing method is applied to the collector, and a composite material layer formed by a positive electrode composition containing the carbon black, the carbon nanotubes, the binding material and the active material is formed on the collector to obtain a positive electrode including the collector and the composite material layer.

[0041] <7> A method for manufacturing a battery, comprising the following positive electrode forming step: <5> The coating liquid for forming the positive electrode manufactured by the manufacturing method is applied to the collector, and a composite material layer formed by a positive electrode composition containing the carbon black, the carbon nanotubes, the binding material and the active material is formed on the collector to obtain a positive electrode including the collector and the composite material layer.

[0042] Effects of the Invention

[0043] According to the present invention, a positive electrode composition of a battery having a small internal resistance and excellent discharge rate characteristics and cycle characteristics is provided. In addition, according to the present invention, a method for manufacturing a positive electrode coating liquid for a battery having a small internal resistance and excellent discharge rate characteristics and cycle characteristics is provided. In addition, according to the present invention, a positive electrode of a battery having a small internal resistance and excellent discharge rate characteristics and cycle characteristics and a method for manufacturing the same are provided. In addition, according to the present invention, a battery having the above-mentioned positive electrode and a method for manufacturing the same are provided. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] [ Figure 1 ] is a schematic diagram used to illustrate the two-dimensional projection image of a primary aggregate.

[0045] [ Figure 2] is a diagram showing a two-dimensional projection image of the primary aggregate of the carbon black (A3) of Production Example A3 obtained using a transmission electron microscope. DETAILED DESCRIPTION

[0046] The preferred embodiments of the present invention are described in detail below. It should be noted that in this specification, carbon black is sometimes abbreviated as "CB" and carbon nanotubes are sometimes abbreviated as "CNT". In addition, in this specification, the wavy line "~" is a symbol used to indicate a numerical range that includes the numerical values ​​recorded before and after it. Specifically, the description of "X~Y" (X, Y are both numerical values) means "above X and below Y".

[0047] <Carbon Black>

[0048] The carbon black of the present embodiment is the following carbon black, that is, when divided into the first primary aggregate, the second primary aggregate, the third primary aggregate and the fourth primary aggregate, the total number of the second primary aggregate and the third primary aggregate (N 2 +N 3 ) relative to the total number of the first primary aggregate, the second primary aggregate, the third primary aggregate, and the fourth primary aggregate (N 1 +N 2 +N 3 +N 4 ), the X value of the first primary aggregate obtained by using formula (X) is greater than 1.7, the X value of the second primary aggregate is less than 1.7, and the Y value obtained by using formula (Y) is less than 1.2, the X value of the third primary aggregate is less than 1.7, the Y value is greater than 1.2, and the Z value obtained by using formula (Z) is less than 2.0, and the X value of the fourth primary aggregate is less than 1.7, the Y value is greater than 1.2, and the Z value is greater than 2.0.

[0049] X=L / W (X)

[0050] Y=P 2 / 4πA (Y)

[0051] Z=(L×W) / A(Z)

[0052] In formulas (X), (Y) and (Z), in the two-dimensional projection image of the primary aggregate obtained by transmission electron microscopy, the Fret diameter (minor diameter) in the minor axis direction of the primary aggregate is W (μm), the Fret diameter (major diameter) in the major axis direction of the primary aggregate is L (μm), the circumference of the primary aggregate is P (μm), and the projected area of ​​the primary aggregate is A (μm). 2 ).

[0053] Figure 1This is a schematic diagram for explaining the two-dimensional projection image of a primary aggregate. The width of the rectangle bounding the primary aggregate is W (μm), the length of the rectangle bounding the primary aggregate is L (μm), the perimeter of the primary aggregate is P (μm), and the projection area of ​​the primary aggregate is A (μm 2 ).

[0054] The first primary aggregate is a primary aggregate having an X value of greater than 1.7 in formula (X). Here, the X value of formula (X) represents the aspect ratio of the primary aggregate, and the greater the difference between the major diameter and the minor diameter, the greater the X value. The X value of the first primary aggregate is greater than 1.7, so it can be called a primary aggregate with a shape close to a linear shape.

[0055] The second primary aggregate is a primary aggregate having an X value of less than 1.7 and a Y value of less than 1.2 of formula (X). Here, the Y value of formula (Y) is an index of the complexity of the primary aggregate, and it can be said that the closer the Y value is to 1, the closer the shape is to a perfect circle. The X value of the second primary aggregate is less than 1.7 and the Y value is less than 1.2, so it can be called a primary aggregate with a shape close to a spheroid.

[0056] The third primary aggregate is a primary aggregate in which the X value of formula (X) is less than 1.7, the Y value of formula (Y) is greater than 1.2, and the Z value of formula (Z) is less than 2.0. Here, the Z value of formula (Z) is the ratio of the area (L×W) of the rectangle circumscribed with the projection diagram of the primary aggregate to the projected area (A) of the primary aggregate. It can be said that the larger the Z value, the more the primary aggregate branches into dendrites. The X value of the third primary aggregate is less than 1.7, the Y value is greater than 1.2, and the Z value is less than 2.0, so it can be called a primary aggregate with a shape close to an ellipsoid.

[0057] The fourth primary aggregate is a primary aggregate in which the X value of formula (X) is less than 1.7, the Y value of formula (Y) is greater than 1.2, and the Z value of formula (Z) is greater than 2.0. The fourth primary aggregate has an X value of less than 1.7, a Y value of greater than 1.2, and a Z value of greater than 2.0, so it can be called a dendritic primary aggregate with many branches.

[0058] According to the inventors' understanding, the second primary aggregates and the third primary aggregates having a shape close to a rotating ellipsoid or an ellipsoid are less likely to cause an increase in the viscosity of the slurry due to entanglement of the primary aggregates with each other than the first primary aggregates and the fourth primary aggregates. In the carbon black of the present embodiment, the total number ratio of the second primary aggregates and the third primary aggregates is 22% or more (preferably 23%), so the dispersibility is excellent and a low-viscosity slurry can be formed.

[0059] The first and fourth primary aggregates are advantageous for the formation of a conductive path, and from the viewpoint of excellent performance as a conductive agent, the first and fourth primary aggregates are preferably present in a predetermined amount or more. 2 +N 3 ) relative to the total number of the first primary aggregate, the second primary aggregate, the third primary aggregate, and the fourth primary aggregate (N 1 +N 2 +N 3 +N 4 ) can be, for example, less than 50%, preferably less than 45%, more preferably less than 40%, and further preferably less than 35%.

[0060] That is, the total number of the second primary aggregate and the third primary aggregate (N 2 +N 3 ) relative to the total number of the first primary aggregate, the second primary aggregate, the third primary aggregate, and the fourth primary aggregate (N 1 +N 2 +N 3 +N 4 ) can be, for example, 22-50%, 22-45%, 22-40%, 22-35%, 23-50%, 23-45%, 23-40% or 23-35%.

[0061] The number ratio of the first aggregates (N 1 ) is not particularly limited, and can be, for example, 25% or more, 30% or more, or 35% or more relative to the total count of the first primary aggregate, the second primary aggregate, the third primary aggregate, and the fourth primary aggregate (N1+N2+N3+N4). In addition, relative to the total count of the first primary aggregate, the second primary aggregate, the third primary aggregate, and the fourth primary aggregate (N1+N2+N3+N4), the number ratio of the first primary aggregate (N 1 ) For example, it may be 70% or less, 65% or less, or 60% or less.

[0062] That is, the number ratio of the first primary aggregates (N 1 ) is not particularly limited and can be, for example, 25-70%, 25-65%, 25-60%, 30-70%, 30-65%, 30-60%, 35-70%, 35-65% or 35-60% relative to the total count of the first primary aggregate, the second primary aggregate, the third primary aggregate and the fourth primary aggregate (N1+N2+N3+N4).

[0063] The number ratio of the second primary aggregates (N 2) is not particularly limited, and can be, for example, 1% or more, 2% or more, or 3% or more relative to the total count of the first primary aggregate, the second primary aggregate, the third primary aggregate, and the fourth primary aggregate (N1+N2+N3+N4). In addition, relative to the total count of the first primary aggregate, the second primary aggregate, the third primary aggregate, and the fourth primary aggregate (N1+N2+N3+N4), the number ratio of the second primary aggregate (N 2 ) For example, it may be 20% or less, 10% or less, or 8% or less.

[0064] That is, the number ratio of the second primary aggregate (N1+N2+N3+N4) to the total number of the first primary aggregate, the second primary aggregate, the third primary aggregate, and the fourth primary aggregate is 2 ) can be, for example, 1-20%, 1-10%, 1-8%, 2-20%, 2-10%, 2-8%, 3-20%, 3-10% or 3-8%.

[0065] The number ratio of the third primary aggregates (N 3 ) is not particularly limited, and can be, for example, 5% or more, 10% or more, or 15% or more relative to the total count of the first primary aggregate, the second primary aggregate, the third primary aggregate, and the fourth primary aggregate (N1+N2+N3+N4). In addition, relative to the total count of the first primary aggregate, the second primary aggregate, the third primary aggregate, and the fourth primary aggregate (N1+N2+N3+N4), the number ratio of the third primary aggregate (N 3 ) For example, it may be 55% or less, 50% or less, or 45% or less.

[0066] That is, relative to the total number of the first primary aggregate, the second primary aggregate, the third primary aggregate, and the fourth primary aggregate (N1+N2+N3+N4), the number ratio of the third primary aggregate (N 3 ) can be, for example, 5-55%, 5-50%, 5-45%, 10-55%, 10-50%, 10-45%, 15-55%, 15-50% or 15-45%.

[0067] The number ratio of the fourth primary aggregate (N 4 ) is not particularly limited, and can be, for example, 5% or more, 10% or more, or 15% or more relative to the total count of the first primary aggregate, the second primary aggregate, the third primary aggregate, and the fourth primary aggregate (N1+N2+N3+N4). In addition, relative to the total count of the first primary aggregate, the second primary aggregate, the third primary aggregate, and the fourth primary aggregate (N1+N2+N3+N4), the number ratio of the fourth primary aggregate (N 4) For example, it may be 45% or less, 40% or less, or 35% or less.

[0068] That is, relative to the total number of the first primary aggregate, the second primary aggregate, the third primary aggregate, and the fourth primary aggregate (N1+N2+N3+N4), the number ratio of the fourth primary aggregate (N 4 ) can be, for example, 5-45%, 5-40%, 5-35%, 10-45%, 10-40%, 10-35%, 15-45%, 15-40% or 15-35%.

[0069] In addition, in this specification, the photographing of the two-dimensional projection image of the primary aggregate obtained by the transmission electron microscope and the image analysis can be performed by the following method.

[0070] First, carbon black was dispersed in chloroform at an ultrasonic output power of 90 W for 10 minutes to loosen secondary aggregates into primary aggregates, which were then collected on a collodion mesh and photographed using a transmission electron microscope at a magnification of 2000.

[0071] Next, the image analysis software "Image-Pro Plus 6.2J (manufactured by Media Cybernetics)" was used to analyze the Feret diameter W (μm) in the short axis direction, the Feret diameter L (μm) in the long axis direction, the perimeter P (μm), the projected area A (μm) of more than 100 carbon black primary aggregates randomly selected from the captured two-dimensional projection image. 2 ) for measurement. Specifically, after filtering the two-dimensional projection image (median filter. Option (option) 7×7. Times: 3), manually extract the brightness range to match the primary aggregate. Select "Size (width)", "Size (length)", "Perimeter", and "Area" from the measurement items for measurement. It should be noted that the measurement is performed after removing the primary aggregate at one end of the two-dimensional projection image, the scale bar, and the background noise.

[0072] For carbon black, the shape of the primary aggregates varies significantly depending on the thermal history during synthesis (for example, thermal decomposition and combustion reaction of fuel oil, thermal decomposition and combustion reaction of raw materials, thermal history caused by rapid cooling and cessation of reaction based on cooling medium, etc.), the collision frequency of primary particles, etc.

[0073] The specific surface area of ​​the carbon black in this embodiment can be, for example, 130 m 2 From the viewpoint of further improving the conductivity-imparting ability, the specific surface area of ​​carbon black is preferably 140 m 2 / g or more, more preferably 150m 2 / g or more, more preferably 160m 2 The specific surface area of ​​carbon black can be increased by reducing the particle size of primary particles, making the particles hollow, making the particle surface porous, and the like.

[0074] In addition, the specific surface area of ​​the carbon black of this embodiment can be, for example, 500 m 2 From the viewpoint of further improving dispersibility, the specific surface area of ​​carbon black is preferably 450 m 2 / g or less, more preferably 400m 2 / g or less.

[0075] That is, the specific surface area of ​​the carbon black of the present embodiment may be, for example, 130 to 500 m 2 / g, 130~450m 2 / g, 130~400m 2 / g, 140~500m 2 / g, 140~450m 2 / g, 140~400m 2 / g, 150~500m 2 / g, 150~450m 2 / g, 150~400m 2 / g, 160~500m 2 / g, 160~450m 2 / g or 160~400m 2 / g.

[0076] In addition, in this specification, the specific surface area is measured according to the A method flow method (thermal conductivity measurement method) of JIS K6217-2:2017.

[0077] The DBP absorption of the carbon black of the present embodiment may be, for example, 150 mL / 100 g or more, preferably 160 mL / 100 g or more, and more preferably 165 mL / 100 g or more. In addition, the DBP absorption of the carbon black of the present embodiment may be, for example, 300 mL / 100 g or less, and more preferably 285 mL / 100 g or less.

[0078] That is, the DBP absorption of the carbon black of the present embodiment may be, for example, 150 to 300 mL / 100 g, 150 to 285 / 100 g, 160 to 300 mL / 100 g, 160 to 285 / 100 g, 165 to 300 mL / 100 g, or 165 to 285 / 100 g.

[0079] The DBP absorption is an indicator for evaluating the ability to absorb dibutyl phthalate (DBP) on the particle surface of carbon black and in the voids formed by the primary aggregates. In carbon black with developed primary aggregates, the number of necks formed by the fusion of primary particles and the voids formed between particles increases, so the DBP absorption increases. If the DBP absorption is large, there is a tendency for the conductivity-imparting ability in the electrode to increase due to the development of the primary aggregates. In addition, it is easy to follow the volume change of the active material accompanying the charge and discharge of the battery, and the battery characteristics such as the cycle characteristics tend to be further improved. In addition, if the DBP absorption is small, there is a tendency to avoid the situation in which the binder in the composite material layer is captured by the primary aggregates of carbon black, and it is easy to maintain good adhesion with the active material and the collector.

[0080] In this specification, the DBP absorption refers to a value obtained by converting a value measured by the method described in Method B of JIS K6221 into a value equivalent to JIS K6217-4:2008 using the following formula (a).

[0081] DBP absorption = (A-10.974) / 0.7833…(a)

[0082] [In the formula, A represents the value of DBP absorption measured by the method described in Method B of JIS K6221.]

[0083] The average primary particle size of the carbon black of the present embodiment may be, for example, less than 35 nm, preferably less than 30 nm, and more preferably less than 25 nm. The average primary particle size of the carbon black of the present embodiment may be, for example, 1 nm or more.

[0084] In the past, carbon black used in the conductive agent of lithium ion secondary batteries was difficult to slurry if the average primary particle size was small (e.g., less than 30 nm), but the carbon black of the present embodiment can easily form a low-viscosity slurry even when the average primary particle size is small (e.g., less than 30 nm). Thus, by being able to use carbon black with a small particle size, high conductivity can be achieved even if the mixing ratio in the composite material layer is low.

[0085] The average primary particle size of carbon black can be obtained by measuring the primary particle sizes of 100 or more carbon black particles randomly selected from a 50,000-fold magnified image of a transmission electron microscope (TEM), and calculating the average value. The primary particles of carbon black have a small aspect ratio and a shape close to a sphere, but are not completely spherical. Therefore, in this embodiment, the largest of the line segments connecting two points on the periphery of the primary particle in the TEM image is used as the primary particle size of carbon black.

[0086] The ash content of the carbon black of the present embodiment may be, for example, 0.05 mass % or less, preferably 0.03 mass % or less, and more preferably 0.02 mass % or less. The ash content may be measured according to JIS K1469:2003, and the ash content may be reduced by classifying the carbon black using a dry cyclone separator or the like.

[0087] The iron content of the carbon black of the present embodiment may be, for example, less than 2500 mass ppb, preferably less than 2300 mass ppb, and more preferably less than 2000 mass ppb. For example, the iron content can be reduced by bringing the carbon black into contact with a magnet.

[0088] The iron content of carbon black can be pre-treated by the acid decomposition method according to JIS K0116:2014 and measured by high-frequency inductively coupled plasma mass spectrometry. Specifically, it can be measured by the following method. First, 1 g of carbon black is accurately weighed in a quartz beaker and heated at 800°C for 3 hours in an air atmosphere using an electric furnace. Then, 10 mL of a mixed acid (70% by mass of hydrochloric acid and 30% by mass of nitric acid) and more than 10 mL of ultrapure water are added to the residue, and heated on a hot plate at 200°C for 1 hour to dissolve it. After cooling, the solution diluted with ultrapure water and adjusted to 25 mL is measured using a high-frequency inductively coupled plasma mass spectrometer (Agilent 8800 manufactured by Agilent).

[0089] If the ash and iron content of carbon black is low, the mixing of foreign matter such as metal and ceramic caused by damage to the device can be more significantly suppressed during the mixing process. In addition, the reduction in conductivity in the electrode caused by the mixing of ash, insulating foreign matter, etc. can also be suppressed. Therefore, carbon black with low ash and iron content can be suitably used in lithium ion secondary batteries that require high safety.

[0090] The method for producing carbon black of the present embodiment is not particularly limited. For example, raw materials such as hydrocarbons can be supplied from a nozzle disposed in the upstream portion of a reactor, carbon black can be produced through thermal decomposition reaction and / or combustion reaction, and captured from a bag filter directly connected to the downstream portion of the reactor.

[0091] The raw materials used are not particularly limited, and gaseous hydrocarbons such as acetylene, methane, ethane, propane, ethylene, propylene, butadiene, etc.; oily hydrocarbons such as toluene, benzene, xylene, gasoline, kerosene, light oil, heavy oil, etc. can be used. Among them, acetylene with less impurities is preferably used. The decomposition heat of acetylene is greater than that of other raw materials, and the temperature in the reactor can be increased. Therefore, the nucleation of carbon black is superior to the particle growth caused by the addition reaction, and the primary particle size of carbon black can be reduced.

[0092] In addition, it is preferred to supply oxygen, carbon dioxide, hydrogen, nitrogen, water vapor, etc. to the reactor separately from the raw materials that become the carbon source. Gases other than these raw materials promote gas stirring in the reactor, increase the frequency of collision and fusion of primary particles of carbon black generated from the raw materials, and therefore, by using gases other than the raw materials, there is a tendency for primary aggregates of carbon black to develop and the DBP absorption amount to increase. As a gas other than the raw material, oxygen is preferably used. If oxygen is used, a part of the raw material is burned, the temperature in the reactor rises, and it is easy to obtain carbon black with a small particle size and a high specific surface area. As a gas other than the raw material, a variety of gases can also be used. The supply position of the gas other than the raw material is preferably the upstream part of the reactor, and the gas other than the raw material is preferably supplied from other nozzles relative to the raw material. Thus, the raw material supplied from the upstream part is also efficiently stirred, and the primary aggregate becomes easy to develop.

[0093] In addition, the inventors of the present application have conducted in-depth research to control the shape of the primary aggregates, and found that supplying a gas other than the raw material to the reactor from a direction orthogonal to the flow direction of the raw material gas is effective for the manufacture of carbon black in the present embodiment. It is believed that in this method, compared with the previous situation in which the raw material gas and the gas other than the raw material are supplied in parallel, the rotation effect has an effect on the generated carbon black, and it becomes easier to form a primary aggregate in the shape of a rotating ellipsoid or an ellipsoid than a linear or branched primary aggregate. It is also found that the ejection speed of the gas other than the raw material into the reactor affects the shape of the primary aggregate.

[0094] In the previous carbon black manufacturing, in order to thermally decompose the raw materials and stop the combustion reaction, a cooling medium such as water is sometimes introduced from the downstream part of the reactor. However, no effect on the development of primary aggregates has been found. On the other hand, the deviation of characteristics may become larger due to the rapid temperature change. Therefore, in the present embodiment, it is preferred not to introduce a cooling medium from the downstream part of the reactor.

[0095] The carbon black of the present embodiment is not limited to the carbon black directly obtained by manufacturing using a reactor as described above. For example, the carbon black of the present embodiment can also be obtained by pulverizing the obtained carbon black and mixing carbon black manufactured under different conditions.

[0096] <First dose>

[0097] The first agent of this embodiment is a mixture of the above-mentioned carbon black and a liquid medium. The first agent of this embodiment can also be called a slurry containing carbon black and a liquid medium.

[0098] The first agent of the present embodiment may further contain a dispersant for assisting the dispersion of carbon black in the liquid medium. That is, the first agent of the present embodiment may be a mixture of the above-mentioned carbon black, the liquid medium and the dispersant.

[0099] As the liquid medium, for example, water, N-methyl-2-pyrrolidone, cyclohexane, methyl ethyl ketone, methyl isobutyl ketone, etc. can be mentioned. Among these, from the viewpoint of dispersibility, N-methyl-2-pyrrolidone is preferred. Sometimes N-methyl-2-pyrrolidone is abbreviated as "NMP".

[0100] The dispersant may be any component as long as it has a function of assisting the dispersion of the conductive material (carbon black) in the liquid medium.

[0101] Examples of the dispersant include polymer dispersants and low molecular weight dispersants. From the viewpoint of long-term dispersion stability of the conductive material (carbon black), polymer dispersants are preferred.

[0102] The dispersant may be, for example, a dispersant selected from the group consisting of polyvinyl alcohol, polyvinyl pyrrolidone, polyvinyl butyral, carboxymethyl cellulose and salts thereof, polyvinyl acetal, polyvinyl acetate, polyvinyl amine, and polyvinyl formal.

[0103] The content of the dispersant in the first agent may be, for example, 1 part by mass or more relative to 100 parts by mass of carbon black, and may be 2 parts by mass or more, 3 parts by mass or more, 4 parts by mass or more, or 5 parts by mass or more from the viewpoint of improving the dispersibility of carbon black. In addition, the content of the dispersant in the first agent may be, for example, 50 parts by mass or less relative to 100 parts by mass of carbon black, and may be 45 parts by mass or less, 40 parts by mass or less, 35 parts by mass or less, 30 parts by mass or less, 25 parts by mass or less, or 20 parts by mass or less from the viewpoint of suppressing the decrease in conductivity caused by the insulating dispersant.

[0104] That is, the content of the dispersant in the first agent can be, for example, 1 to 50 parts by mass, 1 to 45 parts by mass, 1 to 40 parts by mass, 1 to 35 parts by mass, 1 to 30 parts by mass, 1 to 25 parts by mass, 1 to 20 parts by mass, 2 to 50 parts by mass, 2 to 45 parts by mass, 2 to 40 parts by mass, 2 to 35 parts by mass, 2 to 30 parts by mass, 2 to 25 parts by mass, 2 to 20 parts by mass, 3 to 50 parts by mass, 3 to 45 parts by mass, 3-40 parts by mass, 3-35 parts by mass, 3-30 parts by mass, 3-25 parts by mass, 3-20 parts by mass, 4-50 parts by mass, 4-45 parts by mass, 4-40 parts by mass, 4-35 parts by mass, 4-30 parts by mass, 4-25 parts by mass, 4-20 parts by mass, 5-50 parts by mass, 5-45 parts by mass, 5-40 parts by mass, 5-35 parts by mass, 5-30 parts by mass, 5-25 parts by mass or 5-20 parts by mass.

[0105] The solid content concentration of the first dose is not particularly limited, and may be, for example, 1% by mass or more, 2% by mass or more, 3% by mass or more, 4% by mass or more, or 5% by mass or more. In addition, the solid content concentration of the first dose may be, for example, 25% by mass or less, 23% by mass or less, 20% by mass or less, 18% by mass or less, or 15% by mass or less.

[0106] That is, the solid content concentration of the first agent can be, for example, 1-25 mass%, 1-23 mass%, 1-20 mass%, 1-18 mass%, 1-15 mass%, 2-25 mass%, 2-23 mass%, 2-20 mass%, 2-18 mass%, 2-15 mass%, 3-25 mass%, 3-23 mass%, 3-20 mass%, 3-18 mass%, 3-15 mass%, 4-25 mass%, 4-23 mass%, 4-20 mass%, 4-18 mass%, 4-15 mass%, 5-25 mass%, 5-23 mass%, 5-20 mass%, 5-18 mass% or 5-15 mass%.

[0107] If the viscosity of the first agent is too high, strong shearing is applied when mixing with the active material, so there is a situation where the primary aggregates of carbon black are destroyed, the conductivity is reduced, or foreign matter is mixed in due to the wear of the device. On the other hand, if the viscosity of the first agent is too low, there is a situation where carbon black sedimentation is easy to occur in the first agent, and it is difficult to maintain uniformity. In this embodiment, since the above-mentioned carbon black is used, the viscosity of the slurry can be reduced, so that the destruction of the primary aggregates of carbon black is significantly suppressed, and the excellent conductivity imparting ability can be maintained. In addition, the mixing of foreign matter caused by equipment wear is significantly suppressed. That is, in this embodiment, the mixing ratio of the active material in the composite material layer can be increased without damaging the viscosity characteristics and conductivity of the slurry, and the high capacity of batteries such as lithium-ion secondary batteries can be achieved.

[0108] From the viewpoint of obtaining the above-mentioned effect more significantly, the viscosity of the first agent (25°C, shear rate 10s -1 ) can be, for example, 100 mPa·s or more, or 200 mPa·s or more. In addition, from the viewpoint of more significantly obtaining the above-mentioned effect, the viscosity of the first agent (25°C, shear rate 10s -1 ) For example, it can be 1500 mPa·s or less, or 1200 mPa·s or less.

[0109] That is, the viscosity of the first dose (25°C, shear rate 10s -1 ) can be, for example, 100 to 1500 mPa·s, 100 to 1200 mPa·s, 200 to 1500 mPa·s or 200 to 1200 mPa·s.

[0110] <Carbon Nanotubes>

[0111] The carbon nanotubes of this embodiment have an average diameter of 5 to 15 nm.

[0112] By making the average diameter of the carbon nanotubes 5 nm or more, the interaction between the solvent and the conductive material, and the interaction between the conductive materials, becomes smaller, so that it is easy to disperse evenly in the active material, so it is easy to form a conductive path, and it is easier to obtain excellent battery characteristics. By making the average diameter of the carbon nanotubes 15 nm or less, the number of electrical contacts with the active material and the conductive material increases, the effect of imparting conductivity becomes good, and it is easier to obtain excellent battery characteristics.

[0113] The average diameter of carbon nanotubes refers to the average value of diameters measured based on images of carbon nanotubes observed using a transmission electron microscope (TEM). Specifically, it can be obtained in the following manner: using a transmission electron microscope JEM-2000FX (manufactured by JEOL Ltd.), 10 images of carbon nanotubes are taken at a magnification of 200,000 times, and for the obtained images, the diameters of 100 randomly selected carbon nanotubes are measured by image analysis and the arithmetic average is taken.

[0114] From the perspective of making the internal resistance smaller and having better discharge rate characteristics and cycle characteristics, the average diameter of the carbon nanotubes can be less than 14 nm, less than 13 nm, less than 12 nm, less than 11 nm, less than 10 nm, less than 9 nm, less than 8 nm, or less than 7 nm.

[0115] That is, the average diameter of the carbon nanotubes may be, for example, 5 to 15 nm, 5 to 14 nm, 5 to 13 nm, 5 to 12 nm, 5 to 11 nm, 5 to 10 nm, 5 to 9 nm, 5 to 8 nm, or 5 to 7 nm.

[0116] The BET specific surface area of ​​the carbon nanotubes is preferably 170 to 320 m 2 / g. By making the BET specific surface area of ​​carbon nanotubes 170m 2 / g or more, the number of electrical contacts with the active material and the conductive material increases, and the effect of imparting conductivity becomes good, so it is easier to obtain excellent battery characteristics. By making the BET specific surface area of ​​carbon nanotubes 320m 2 When the solvent has a concentration of 0.1447 W or less and the interaction between the solvent and the conductive material and the interaction between the conductive materials is reduced, the solvent can be easily dispersed uniformly in the active material, thereby easily forming a conductive path and easily obtaining excellent battery characteristics.

[0117] The BET specific surface area of ​​the carbon nanotubes can be measured by a static volumetric method in accordance with JIS Z8830 using nitrogen as an adsorbent.

[0118] From the perspective of lowering the internal resistance and improving the discharge rate characteristics and cycle characteristics, the BET specific surface area of ​​carbon nanotubes can be 180 m 2 / g or more, 190m 2 / g or more, 200m 2 / g or more, 210m 2 / g or more, 220m 2 / g or more, 230m 2 / g or more, 240m 2 / g or more, 250m 2 / g or more, 260m 2 / g or more, 270m 2 / g or more, 280m 2 / g or above or 290m 2 In addition, from the perspective of making the internal resistance smaller and the discharge rate characteristics and cycle characteristics more excellent, the BET specific surface area of ​​the carbon nanotubes can be 310 m 2 / g or less.

[0119] That is, the BET specific surface area of ​​carbon nanotubes can be, for example, 170 to 320 m 2 / g, 180~320m 2 / g, 190~320m 2 / g, 200~320m 2 / g, 210~320m 2 / g, 220~320m 2 / g, 230~320m 2 / g, 240~320m 2 / g, 250~320m 2 / g, 260~320m 2 / g, 270~320m 2 / g, 280~320m 2 / g, 290~320m 2 / g, 170~310m 2 / g, 180~310m 2 / g, 190~310m 2 / g, 200~310m 2 / g, 210~310m 2 / g, 220~310m 2 / g, 230~310m 2 / g, 240~310m 2 / g, 250~310m 2 / g, 260~310m 2 / g, 270~310m2 / g, 280~310m 2 / g or 290~310m 2 / g.

[0120] The ratio of the average diameter of carbon black of carbon nanotubes to the BET specific surface area (average diameter / BET specific surface area) is preferably 0.01 to 0.1 nm / (m 2 / g). The above ratio (average diameter / BET specific surface area) is the value obtained by dividing the average diameter of the carbon nanotubes by the BET specific surface area of ​​the carbon nanotubes. By setting the ratio (average diameter / BET specific surface area) to 0.01nm / (m 2 / g) or more, the carbon nanotubes are less entangled with each other, and are easily dispersed evenly in the active material, so that a conductive path is easily formed, and excellent battery characteristics are more easily obtained. By making the ratio (average diameter / BET specific surface area) 0.1nm / (m 2 / g) or less, the number of carbon nanotubes per unit weight increases, and electricity can be efficiently conducted throughout the entire active material, thereby obtaining excellent battery characteristics.

[0121] From the viewpoint of making the internal resistance smaller and the discharge rate characteristics and cycle characteristics more excellent, the ratio (average diameter / BET specific surface area) can be 0.09 nm / (m 2 / g) or less, 0.08nm / (m 2 / g) or less, 0.07nm / (m 2 / g) or less, 0.06nm / (m 2 / g) or less, 0.05nm / (m 2 / g) or less, 0.04nm / (m 2 / g) or less than 0.03nm / (m 2 / g) or less.

[0122] That is, the ratio (average diameter / BET specific surface area) may be, for example, 0.01 to 0.1 nm, 0.01 to 0.09 nm / (m 2 / g)、0.01~0.08nm / (m 2 / g)、0.01~0.07nm / (m 2 / g)、0.01~0.06nm / (m 2 / g)、0.01~0.05nm / (m 2 / g)、0.01~0.04nm / (m 2 / g) or 0.01~0.03nm / (m 2 / g).

[0123] The above-mentioned carbon nanotubes can be produced by a conventionally known method for producing carbon nanotubes. For example, the carbon nanotubes can be produced by allowing a powdered catalyst obtained by supporting iron on magnesium oxide to be present on the entire horizontal cross-sectional surface of a vertical reactor, allowing methane to flow in the reactor in a vertical direction, allowing methane to contact the above-mentioned catalyst at 500 to 1200° C., and then subjecting the obtained product (unoxidized carbon nanotubes) to oxidation treatment. The above-mentioned method for producing carbon nanotubes can produce carbon nanotubes having an average diameter of 5 to 15 nm formed by multiple layers of graphene layers.

[0124] The oxidation treatment of the above-mentioned product can be, for example, a calcination treatment. The temperature of the calcination treatment is not particularly limited, and for example, it can be 300 to 1000°C. The temperature of the calcination treatment is affected by the atmosphere gas, so when the oxygen concentration is high, it is preferred to carry out the calcination treatment at a lower temperature, and when the oxygen concentration is low, it is preferred to carry out the calcination treatment at a higher temperature. Specifically, as the calcination treatment of the product, there can be cited a method of calcining in the atmosphere within the range of ±50°C of the combustion peak temperature of the carbon nanotubes before the oxidation treatment, and when the oxygen concentration is higher than the atmosphere, the calcination is carried out in a temperature range lower than the calcination peak temperature, and when the oxygen concentration is lower than the atmosphere, a temperature range higher than the calcination peak temperature is selected. In particular, when the calcination treatment of the carbon nanotubes before the oxidation treatment is carried out in the atmosphere, it is preferably carried out within the range of ±15°C of the combustion peak temperature of the carbon nanotubes before the oxidation treatment.

[0125] The oxidation treatment of the above-mentioned product may be a treatment based on hydrogen peroxide, mixed acid, nitric acid, etc. As a method for treating the above-mentioned product with hydrogen peroxide, for example, the following method can be mentioned: the above-mentioned product is mixed in a 34.5% hydrogen peroxide aqueous solution in a manner of 0.01 to 10% by mass, and reacted at a temperature of 0 to 100° C. for 0.5 to 48 hours. In addition, as a method for treating the above-mentioned product with a mixed acid, for example, the above-mentioned product is mixed in a mixed solution of concentrated sulfuric acid and concentrated nitric acid (concentrated sulfuric acid: concentrated nitric acid = 3:1) in a manner of 0.01 to 10% by mass, and reacted at a temperature of 0 to 100° C. for 0.5 to 48 hours. The mixing ratio of the mixed acid (concentrated sulfuric acid: concentrated nitric acid) can be adjusted in the range of 1:10 to 10:1 according to the amount of single-walled carbon nanotubes in the above-mentioned product. Examples of the method for treating the product with nitric acid include mixing the product in nitric acid having a concentration of 40 to 80% by mass so as to give 0.01 to 10% by mass and reacting the mixture at 60 to 150° C. for 0.5 to 48 hours.

[0126] By subjecting the above product to oxidation treatment, impurities such as amorphous carbon and single-layer carbon nanotubes with low heat resistance in the product can be selectively removed, and the purity of multi-layer graphene layers, especially 2-5-layer carbon nanotubes, can be improved. At the same time, by subjecting the product to oxidation treatment, functional groups can be added to the surface of the carbon nanotubes, thereby improving the affinity with the liquid medium and the dispersant and improving the dispersibility. Among the above oxidation treatments, treatment using nitric acid is preferred.

[0127] The above oxidation treatment may be performed immediately after obtaining the carbon nanotubes before oxidation treatment, or after other purification treatments. For example, when iron / magnesium oxide is used as a catalyst, purification treatment using an acid such as hydrochloric acid may be performed to remove the catalyst before oxidation treatment, and then oxidation treatment may be performed; purification treatment may also be performed after oxidation treatment to remove the catalyst.

[0128] <Second dose>

[0129] The second agent of this embodiment is a mixture of the carbon nanotubes and the liquid medium. The second agent of this embodiment can also be called a slurry containing carbon nanotubes and the liquid medium.

[0130] The second agent of this embodiment may further contain a dispersant for assisting the dispersion of the carbon nanotubes in the liquid medium. That is, the second agent of this embodiment may be a mixture of the carbon nanotubes, the liquid medium and the dispersant.

[0131] Examples of the liquid medium include water, N-methyl-2-pyrrolidone, cyclohexane, methyl ethyl ketone, methyl isobutyl ketone, etc. Among these, N-methyl-2-pyrrolidone is preferred from the viewpoint of dispersibility.

[0132] The dispersant may be any component as long as it has a function of assisting the dispersion of the conductive material (carbon nanotubes) in the liquid medium.

[0133] Examples of the dispersant include polymer dispersants and low molecular weight dispersants. From the viewpoint of long-term dispersion stability of the conductive material (carbon nanotube), polymer dispersants are preferred.

[0134] The dispersant may be, for example, a dispersant selected from the group consisting of polyvinyl alcohol, polyvinyl pyrrolidone, polyvinyl butyral, carboxymethyl cellulose and salts thereof, polyvinyl acetal, polyvinyl acetate, polyvinyl amine, and polyvinyl formal.

[0135] The content of the dispersant in the second agent may be, for example, 1 part by mass or more relative to 100 parts by mass of the carbon nanotubes, and may be 5 parts by mass or more, 10 parts by mass or more, 15 parts by mass or more, or 20 parts by mass or more from the viewpoint of improving the dispersibility of the carbon nanotubes. In addition, the content of the dispersant in the second agent may be, for example, 50 parts by mass or less relative to 100 parts by mass of the carbon nanotubes, and may be 45 parts by mass or less, or 40 parts by mass or less from the viewpoint of suppressing the reduction in conductivity caused by the insulating dispersant.

[0136] That is, the content of the dispersant in the second agent can be, for example, 1 to 50 parts by mass, 1 to 45 parts by mass, 1 to 40 parts by mass, 5 to 50 parts by mass, 5 to 45 parts by mass, 5 to 40 parts by mass, 10 to 50 parts by mass, 10 to 45 parts by mass, 10 to 40 parts by mass, 15 to 50 parts by mass, 15 to 45 parts by mass, 15 to 40 parts by mass, 20 to 50 parts by mass, 20 to 45 parts by mass or 20 to 40 parts by mass relative to 100 parts by mass of carbon nanotubes.

[0137] The solid content concentration of the second dose is not particularly limited, and may be, for example, 0.1% by mass or more, 1% by mass or more, 2% by mass or more, or 3% by mass or more. In addition, the solid content concentration of the second dose may be, for example, 10% by mass or less, 9% by mass or less, 8% by mass or less, or 7% by mass or less.

[0138] That is, the solid content concentration of the second agent can be, for example, 0.1-10 mass%, 0.1-9 mass%, 0.1-8 mass%, 0.1-7 mass%, 1-10 mass%, 1-9 mass%, 1-8 mass%, 1-7 mass%, 2-10 mass%, 2-9 mass%, 2-8 mass%, 2-7 mass%, 3-10 mass%, 3-9 mass%, 3-8 mass% or 3-7 mass%.

[0139] If the viscosity of the second agent is too high, strong shear is applied when kneading with the active material, so there are cases where the primary aggregates of carbon black mixed together are destroyed and the conductivity is reduced; or foreign matter is mixed in due to wear of the device. On the other hand, if the viscosity of the second agent is too low, the carbon nanotubes are easily precipitated in the second agent, and it is sometimes difficult to maintain uniformity. That is, in this embodiment, when the second agent has the preferred viscosity described below, the above effect is more significantly obtained.

[0140] From the viewpoint of obtaining the above-mentioned effect more significantly, the viscosity of the second agent (25°C, shear rate 10s -1 ) can be, for example, 10 mPa·s or more, or 50 mPa·s or more. In addition, from the viewpoint of more significantly obtaining the above-mentioned effect, the viscosity of the second agent (25°C, shear rate 10s -1) For example, it can be 1000 mPa·s or less, or 500 mPa·s or less.

[0141] That is, the viscosity of the second agent (25°C, shear rate 10s -1 ) can be, for example, 10 to 1000 mPa·s, 10 to 500 mPa·s, 50 to 1000 mPa·s or 50 to 500 mPa·s.

[0142] <Third dose>

[0143] The third agent contains a bonding material and a liquid medium. The third agent can also be called a mixture of a bonding material and a liquid medium.

[0144] As the bonding material, for example, polyvinylidene fluoride, polytetrafluoroethylene, styrene butadiene copolymer, (meth) acrylate copolymer can be cited. The structure of the polymer of the bonding material can be, for example, a random copolymer, an alternating copolymer, a graft copolymer, a block copolymer, etc. As the bonding material, polyvinylidene fluoride is preferred from the viewpoint of excellent voltage resistance.

[0145] Examples of the liquid medium include water, N-methyl-2-pyrrolidone, cyclohexane, methyl ethyl ketone, methyl isobutyl ketone, etc. Among these, N-methyl-2-pyrrolidone is preferred from the viewpoint of dispersibility.

[0146] <Active substances>

[0147] The active material may be any material as long as it can reversibly absorb and release cations. The active material may also be referred to as a positive electrode active material.

[0148] The active material is not particularly limited, and for example, known active materials used in lithium ion secondary batteries can be used without particular limitation. Examples of the active material include lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, nickel·manganese·lithium cobalt oxide, and lithium iron phosphate.

[0149] The active material may have a volume resistivity of 1×10 4 A lithium-containing composite oxide containing manganese or a polyanion compound containing lithium having a thickness of Ω·cm or more. Examples of the lithium-containing composite oxide containing manganese include LiMnO 2 、LiMnO 3 、LiMn 2 O 3 , Li 1+x Mn 2-x O 4 (where x = 0 to 0.33) etc. lithium manganate; LiMn x Ni y Co z O 2(where x+y+z=1, 0≤y<1, 0≤z<1, 0≤x<1), Li 1+x Mn 2-x-y M y O 4 (where x = 0 to 0.33, y = 0 to 1.0, 2-xy>0), LiMn 2-x M x O 2 (where x = 0.01 to 0.1), Li 2 Mn 3 MO 8 The lithium-containing polyanion compound includes LiFePO 4 、LiMnPO 4 , Li 2 MPO 4 F (wherein M is at least one metal selected from Co, Ni, Fe, Cr, and Zn). M in each composition formula is at least one selected from the group consisting of Fe, Co, Ni, Al, Cu, Mg, Cr, Zn, and Ta.

[0150] From the viewpoint that the bonding between the conductive material and the binder is sufficiently excellent and a battery with better cycle characteristics can be easily obtained, the average particle size (D 50 ) can be 20 μm or less or 10 μm or less. The average particle size (D 50 ) can be measured by laser scattering method. The average particle size of the active material (D 50 ) can be, for example, greater than 1 μm.

[0151] <Positive Electrode Forming Coating Solution>

[0152] The positive electrode forming coating liquid of the present embodiment may contain carbon black, carbon nanotubes, a binder, an active material, and a liquid medium. The positive electrode forming coating liquid may further contain a dispersant (dispersant for conductive material).

[0153] In the positive electrode forming coating liquid of the present embodiment, examples of carbon black, carbon nanotubes, a binder, an active material, a dispersant, and a liquid medium include the same substances as those described above.

[0154] The positive electrode forming coating liquid of the present embodiment can be produced by, for example, the following production method.

[0155] The method for manufacturing a coating liquid for forming a positive electrode of the present embodiment includes: a mixing step of mixing the above-mentioned carbon black with a first liquid medium to obtain a first agent containing carbon black and the first liquid medium; and a coating liquid forming step of mixing the first agent, a second agent containing carbon nanotubes and a second liquid medium, a third agent containing a binding material and a third liquid medium, and an active material to form a coating liquid for forming a positive electrode.

[0156] In the method for producing the positive electrode forming coating solution of the present embodiment, examples of the first agent, the second agent, the third agent, and the active material include the same ones as described above.

[0157] In the mixing process, the method for mixing carbon black with the first liquid medium is not particularly limited, and can be implemented using a known method (for example, stirring and mixing based on a ball mill, a sand mill, a twin-screw mixer, a self-rotating and revolving mixer, a planetary mixer, a disperser, etc.).

[0158] In the coating liquid forming process, the method of mixing the first agent, the second agent, and the third agent with the active material is not particularly limited, and can be implemented by a known method (for example, stirring and mixing based on a ball mill, a sand mill, a twin-screw mixer, a self-rotating revolution mixer, a planetary mixer, a disperser, etc.). The first agent, the second agent, the third agent, and the active material can be mixed at the same time or in sequence. For example, the active material can be mixed after the first agent, the second agent, and the third agent are mixed, or the first agent and the third agent can be mixed, followed by the second agent, and finally the active material.

[0159] The content of carbon black in the coating liquid for forming the positive electrode may be, for example, 5 parts by mass or more relative to the total of 100 parts by mass of carbon black and carbon nanotubes, and may be 10 parts by mass or more, 15 parts by mass or more, 20 parts by mass or more, 25 parts by mass or more, 30 parts by mass or more, 35 parts by mass or more, 40 parts by mass or more, 45 parts by mass or more, 50 parts by mass or more, 55 parts by mass or more, 60 parts by mass or more, or 65 parts by mass or more relative to the total of 100 parts by mass of carbon black and carbon nanotubes, and may be 99 parts by mass or less relative to the total of 100 parts by mass of carbon black and carbon nanotubes, and may be 95 parts by mass or less, 90 parts by mass or less, 85 parts by mass or less, 80 parts by mass or less, or 75 parts by mass or less relative to the total of 100 parts by mass of carbon black and carbon nanotubes, and may be 95 parts by mass or less, 90 parts by mass or less, 85 parts by mass or less, 80 parts by mass or less, or 75 parts by mass or less relative to the total of 100 parts by mass of carbon black and carbon nanotubes.

[0160] That is, the content of carbon black in the positive electrode forming coating liquid can be, for example, 5 to 99 parts by mass, 5 to 95 parts by mass, 5 to 90 parts by mass, 5 to 85 parts by mass, 5 to 80 parts by mass, 5 to 75 parts by mass, 10 to 99 parts by mass, 10 to 95 parts by mass, 10 to 90 parts by mass, 10 to 85 parts by mass, 10 to 80 parts by mass, 10 to 75 parts by mass, 15 to 99 parts by mass, 15 to 95 parts by mass, 15 to 90 parts by mass, 15 to 85 parts by mass, 15 to 80 parts by mass, 10 to 75 parts by mass, 15 to 99 parts by mass, 15 to 95 parts by mass, 15 to 90 parts by mass, 15 to 85 parts by mass, 15 to 80 parts by mass, parts by mass, 15 to 75 parts by mass, 20 to 99 parts by mass, 20 to 95 parts by mass, 20 to 90 parts by mass, 20 to 85 parts by mass, 20 to 80 parts by mass, 20 to 75 parts by mass, 25 to 99 parts by mass, 25 to 95 parts by mass, 25 to 90 parts by mass, 25 to 85 parts by mass, 25 to 80 parts by mass, 25 to 75 parts by mass, 30 to 99 parts by mass, 30 to 95 parts by mass, 30 to 90 parts by mass, 30 to 85 parts by mass, 30 to 80 parts by mass, 30 to 75 parts by mass, 35 to 99 parts by mass, 35-95 parts by mass, 35-90 parts by mass, 35-85 parts by mass, 35-80 parts by mass, 35-75 parts by mass, 40-99 parts by mass, 40-95 parts by mass, 40-90 parts by mass, 40-85 parts by mass, 40-80 parts by mass, 40-75 parts by mass, 45-99 parts by mass, 45-95 parts by mass, 45-90 parts by mass, 45-85 parts by mass, 45-80 parts by mass, 45-75 parts by mass, 50-99 parts by mass, 50-95 parts by mass, 50-90 parts by mass, 50-8 5 parts by mass, 50 to 80 parts by mass, 50 to 75 parts by mass, 55 to 99 parts by mass, 55 to 95 parts by mass, 55 to 90 parts by mass, 55 to 85 parts by mass, 55 to 80 parts by mass, 55 to 75 parts by mass, 60 to 99 parts by mass, 60 to 95 parts by mass, 60 to 90 parts by mass, 60 to 85 parts by mass, 60 to 80 parts by mass, 60 to 75 parts by mass, 65 to 99 parts by mass, 65 to 95 parts by mass, 65 to 90 parts by mass, 65 to 85 parts by mass, 65 to 80 parts by mass or 65 to 75 parts by mass.

[0161] The content of carbon nanotubes in the positive electrode forming coating liquid may be, for example, 1 part by mass or more relative to a total of 100 parts by mass of carbon black and carbon nanotubes, and may be 5 parts by mass or more, 10 parts by mass or more, 15 parts by mass or more, 20 parts by mass or more, or 25 parts by mass or more from the viewpoint of making the internal resistance smaller and the viewpoint of making the discharge rate characteristics and the cycle characteristics more excellent. In addition, the content of carbon nanotubes in the positive electrode forming coating liquid may be, for example, 90 parts by mass or less, 85 parts by mass or less, 80 parts by mass or less, 75 parts by mass or less, 70 parts by mass or less, 65 parts by mass or less, 60 parts by mass or less, 55 parts by mass or less, 50 parts by mass or less, 45 parts by mass or less, 40 parts by mass or more, or 35 parts by mass or less relative to a total of 100 parts by mass of carbon black and carbon nanotubes.

[0162] That is, the content of the carbon nanotubes in the positive electrode forming coating liquid can be, for example, 1 to 90 parts by mass, 1 to 85 parts by mass, 1 to 80 parts by mass, 1 to 75 parts by mass, 1 to 70 parts by mass, 1 to 65 parts by mass, 1 to 60 parts by mass, 1 to 55 parts by mass, 1 to 50 parts by mass, 1 to 45 parts by mass, 1 to 40 parts by mass, 1 to 35 parts by mass, 5 to 90 parts by mass, 5 to 85 parts by mass, 5 to 80 parts by mass, 5 ... 5 parts by mass, 5 to 70 parts by mass, 5 to 65 parts by mass, 5 to 60 parts by mass, 5 to 55 parts by mass, 5 to 50 parts by mass, 5 to 45 parts by mass, 5 to 40 parts by mass, 5 to 35 parts by mass, 10 to 90 parts by mass, 10 to 85 parts by mass, 10 to 80 parts by mass, 10 to 75 parts by mass, 10 to 70 parts by mass, 10 to 65 parts by mass, 10 to 60 parts by mass, 10 to 55 parts by mass, 10 to 50 parts by mass, 10 to 45 parts by mass, 10 to 40 parts by mass , 10 to 35 parts by mass, 15 to 90 parts by mass, 15 to 85 parts by mass, 15 to 80 parts by mass, 15 to 75 parts by mass, 15 to 70 parts by mass, 15 to 65 parts by mass, 15 to 60 parts by mass, 15 to 55 parts by mass, 15 to 50 parts by mass, 15 to 45 parts by mass, 15 to 40 parts by mass, 15 to 35 parts by mass, 20 to 90 parts by mass, 20 to 85 parts by mass, 20 to 80 parts by mass, 20 to 75 parts by mass, 20 to 70 parts by mass, 20 to 6 5 parts by mass, 20 to 60 parts by mass, 20 to 55 parts by mass, 20 to 50 parts by mass, 20 to 45 parts by mass, 20 to 40 parts by mass, 20 to 35 parts by mass, 25 to 90 parts by mass, 25 to 85 parts by mass, 25 to 80 parts by mass, 25 to 75 parts by mass, 25 to 70 parts by mass, 25 to 65 parts by mass, 25 to 60 parts by mass, 25 to 55 parts by mass, 25 to 50 parts by mass, 25 to 45 parts by mass, 25 to 40 parts by mass or 25 to 35 parts by mass.

[0163] Based on the total mass of the solid components in the positive electrode forming coating liquid, the total content of carbon nanotubes and carbon black in the positive electrode forming coating liquid can be, for example, 0.1 mass% or more, and from the viewpoint of making the internal resistance smaller, and the discharge rate characteristics and cycle characteristics are better, it can be 0.3 mass% or more, 0.5 mass% or more, 0.7 mass% or more, or 0.9 mass% or more. In addition, based on the total mass of the solid components in the positive electrode forming coating liquid, the total content of carbon nanotubes and carbon black in the positive electrode forming coating liquid can be, for example, 5 mass% or less, and from the viewpoint of making the internal resistance smaller, and the discharge rate characteristics and cycle characteristics are better, it can be 4 mass% or less, 3 mass% or less, 2 mass% or less, or 1.5 mass% or less.

[0164] That is, based on the total mass of the solid components in the positive electrode forming coating liquid, the total content of carbon nanotubes and carbon black in the positive electrode forming coating liquid can be, for example, 0.1 to 5 mass%, 0.1 to 4 mass%, 0.1 to 3 mass%, 0.1 to 2 mass%, 0.1 to 1.5 mass%, 0.3 to 5 mass%, 0.3 to 4 mass%, 0.3 to 3 mass%, 0.3 to 2 mass%, 0.3 to 1.5 mass%, 0.5 to 5 mass%, 0.5 to 4 mass%, 0.5 to 3 mass%, 0.5 to 2 mass%, 0.5 to 1.5 mass%, 0.7 to 5 mass%, 0.7 to 4 mass%, 0.7 to 3 mass%, 0.7 to 2 mass%, 0.7 to 1.5 mass%, 0.9 to 5 mass%, 0.9 to 4 mass%, 0.9 to 3 mass%, 0.9 to 2 mass% or 0.9 to 1.5 mass%.

[0165] Based on the total mass of the solid components in the positive electrode forming coating liquid, the content of the binding material in the positive electrode forming coating liquid can be, for example, 0.1% by mass or more, from the viewpoint of making the internal resistance smaller, and the viewpoint of the discharge rate characteristics and the cycle characteristics being more excellent, it can be 0.5% by mass or more, 1% by mass or more, or 1.5% by mass or more. In addition, based on the total mass of the solid components in the positive electrode forming coating liquid, the content of the binding material in the positive electrode forming coating liquid can be, for example, 10% by mass or less, from the viewpoint of making the internal resistance smaller, and the viewpoint of the discharge rate characteristics and the cycle characteristics being more excellent, it can be 9% by mass or less, 8% by mass or less, 7% by mass or less, 6% by mass or less, 5% by mass or less, 4% by mass or less, or 3% by mass or less.

[0166] That is, based on the total mass of the solid components in the positive electrode forming coating liquid, the content of the binder in the positive electrode forming coating liquid can be, for example, 0.1 to 10 mass%, 0.1 to 9 mass%, 0.1 to 8 mass%, 0.1 to 7 mass%, 0.1 to 6 mass%, 0.1 to 5 mass%, 0.1 to 4 mass%, 0.1 to 3 mass%, 0.5 to 10 mass%, 0.5 to 9 mass%, 0.5 to 8 mass%, 0.5 to 7 mass%, 0.5 to 6 mass%. % by mass, 0.5-5% by mass, 0.5-4% by mass, 0.5-3% by mass, 1-10% by mass, 1-9% by mass, 1-8% by mass, 1-7% by mass, 1-6% by mass, 1-5% by mass, 1-4% by mass, 1-3% by mass, 1.5-10% by mass, 1.5-9% by mass, 1.5-8% by mass, 1.5-7% by mass, 1.5-6% by mass, 1.5-5% by mass, 1.5-4% by mass or 1.5-3% by mass.

[0167] Based on the total mass of the solid components in the positive electrode forming coating liquid, the content of the active material in the positive electrode forming coating liquid can be, for example, 90% by mass or more, and from the viewpoint of better discharge rate characteristics and cycle characteristics, it can be 92% by mass or more, 94% by mass or more, or 96% by mass or more. In addition, based on the total mass of the solid components in the positive electrode forming coating liquid, the content of the active material in the positive electrode forming coating liquid can be, for example, 99.5% by mass or less, and from the viewpoint of making the internal resistance smaller, it can be 99% by mass or less or 98% by mass or less.

[0168] That is, based on the total mass of the solid components in the positive electrode forming coating liquid, the content of the active material in the positive electrode forming coating liquid can be, for example, 90-99.5 mass%, 90-99 mass%, 90-98 mass%, 92-99.5 mass%, 92-99 mass%, 92-98 mass%, 94-99.5 mass%, 94-99 mass%, 94-98 mass%, 96-99.5 mass%, 96-99 mass% or 96-98 mass%.

[0169] Based on the total mass of the solid components in the positive electrode forming coating liquid, the content of the dispersant in the positive electrode forming coating liquid can be, for example, 0.05 mass % or more, 0.1 mass % or more, or 0.15 mass % or more. In addition, based on the total mass of the solid components in the positive electrode forming coating liquid, the content of the dispersant in the positive electrode forming coating liquid can be, for example, 0.8 mass % or less, 0.5 mass % or less, or 0.2 mass % or less.

[0170] That is, based on the total mass of the solid components in the positive electrode forming coating liquid, the content of the dispersant in the positive electrode forming coating liquid can be, for example, 0.05-0.8 mass%, 0.05-0.5 mass%, 0.05-0.2 mass%, 0.1-0.8 mass%, 0.1-0.5 mass%, 0.1-0.2 mass%, 0.15-0.8 mass%, 0.15-0.5 mass% or 0.15-0.2 mass%.

[0171] The solid content concentration of the coating liquid for positive electrode formation can be, for example, 63% by mass or more, and can be 65% by mass or more, 66% by mass or more, or 67% by mass or more from the viewpoint of shortening the time for drying the liquid medium when manufacturing the positive electrode, and can further suppress the migration of the conductive material when the liquid medium is dried. In addition, the solid content concentration of the coating liquid for positive electrode formation can be, for example, 80% by mass or less, and can be 78% by mass or less, 76% by mass or less, 74% by mass or less, 72% by mass or less, or 70% by mass or less from the viewpoint of making the coating film smoother when manufacturing the positive electrode, and the viewpoint of making the deviation of the internal resistance of the battery smaller.

[0172] That is, the solid content concentration of the positive electrode forming coating liquid can be, for example, 63-80 mass%, 63-78 mass%, 63-76 mass%, 63-74 mass%, 63-72 mass%, 63-70 mass%, 65-80 mass%, 65-78 mass%, 65-76 mass%, 65-74 mass%, 65-72 mass%, 65-70 mass%, 66-80 mass%, 66-78 mass%, 66-76 mass%, 66-74 mass%, 66-72 mass%, 66-70 mass%, 67-80 mass%, 67-78 mass%, 67-76 mass%, 67-74 mass%, 67-72 mass% or 67-70 mass%.

[0173] <Positive electrode>

[0174] The positive electrode of this embodiment includes: a composite material layer formed of a positive electrode composition; and a current collector.

[0175] The positive electrode composition may be a composition containing a solid component of a positive electrode forming coating liquid, or may be a substance obtained by removing at least a portion of a liquid medium from a positive electrode forming coating liquid. That is, the positive electrode composition may be a composition containing carbon black, carbon nanotubes, a binding material, and an active material. The positive electrode composition may further contain a dispersant.

[0176] The content of carbon black in the positive electrode composition may be, for example, 5 parts by mass or more relative to 100 parts by mass of the total of carbon black and carbon nanotubes, and may be 10 parts by mass or more, 15 parts by mass or more, 20 parts by mass or more, 25 parts by mass or more, 30 parts by mass or more, 35 parts by mass or more, 40 parts by mass or more, 45 parts by mass or more, 50 parts by mass or more, 55 parts by mass or more, 60 parts by mass or more, or 65 parts by mass or more relative to 100 parts by mass of the total of carbon black and carbon nanotubes. In addition, the content of carbon black in the positive electrode composition may be, for example, 99 parts by mass or less relative to 100 parts by mass of the total of carbon black and carbon nanotubes, and may be 95 parts by mass or less, 90 parts by mass or less, 85 parts by mass or less, 80 parts by mass or less, or 75 parts by mass or less relative to 100 parts by mass of the total of carbon black and carbon nanotubes.

[0177] That is, the content of carbon black in the positive electrode composition can be, for example, 5 to 99 parts by mass, 5 to 95 parts by mass, 5 to 90 parts by mass, 5 to 85 parts by mass, 5 to 80 parts by mass, 5 to 75 parts by mass, 10 to 99 parts by mass, 10 to 95 parts by mass, 10 to 90 parts by mass, 10 to 85 parts by mass, 10 to 80 parts by mass, 10 to 75 parts by mass, 15 to 99 parts by mass, 15 to 95 parts by mass, 15 to 90 parts by mass, 15 to 85 parts by mass, 15 to 80 parts by mass, 10 to 75 parts by mass, 15 to 99 parts by mass, 15 to 95 parts by mass, 15 to 90 parts by mass, 15 to 85 parts by mass, 15 to 80 parts by mass, parts by weight, 15 to 75 parts by weight, 20 to 99 parts by weight, 20 to 95 parts by weight, 20 to 90 parts by weight, 20 to 85 parts by weight, 20 to 80 parts by weight, 20 to 75 parts by weight, 25 to 99 parts by weight, 25 to 95 parts by weight, 25 to 90 parts by weight, 25 to 85 parts by weight, 25 to 80 parts by weight, 25 to 75 parts by weight, 30 to 99 parts by weight, 30 to 95 parts by weight, 30 to 90 parts by weight, 30 to 85 parts by weight, 30 to 80 parts by weight, 30 to 75 parts by weight, 35 to 99 parts by weight, 30 to 99 parts by weight, 30 to 95 parts by weight, 30 to 90 parts by weight, 30 to 85 parts by weight, 30 to 80 parts by weight, 30 to 75 parts by weight, 35 to 99 parts by weight, 30 to 99 parts by weight 5-95 parts by mass, 35-90 parts by mass, 35-85 parts by mass, 35-80 parts by mass, 35-75 parts by mass, 40-99 parts by mass, 40-95 parts by mass, 40-90 parts by mass, 40-85 parts by mass, 40-80 parts by mass, 40-75 parts by mass, 45-99 parts by mass, 45-95 parts by mass, 45-90 parts by mass, 45-85 parts by mass, 45-80 parts by mass, 45-75 parts by mass, 50-99 parts by mass, 50-95 parts by mass, 50-90 parts by mass, 50-85 75 parts by mass, 65-99 parts by mass, 65-95 parts by mass, 65-90 parts by mass, 65-85 parts by mass, 65-80 parts by mass, 65-75 parts by mass, 60-99 parts by mass, 60-95 parts by mass, 60-90 parts by mass, 60-85 parts by mass, 60-80 parts by mass, 60-75 parts by mass, 65-99 parts by mass, 65-95 parts by mass, 65-90 parts by mass, 65-85 parts by mass, 65-80 parts by mass or 65-75 parts by mass.

[0178] The content of carbon nanotubes in the positive electrode composition may be, for example, 1 part by mass or more relative to a total of 100 parts by mass of carbon black and carbon nanotubes, and may be 5 parts by mass or more, 10 parts by mass or more, 15 parts by mass or more, 20 parts by mass or more, or 25 parts by mass or more from the viewpoint of making the internal resistance smaller and the viewpoint of making the discharge rate characteristics and cycle characteristics more excellent. In addition, the content of carbon nanotubes in the positive electrode composition may be, for example, 90 parts by mass or less, 85 parts by mass or less, 80 parts by mass or less, 75 parts by mass or less, 70 parts by mass or less, 65 parts by mass or less, 60 parts by mass or less, 55 parts by mass or less, 50 parts by mass or less, 45 parts by mass or less, 40 parts by mass or more, or 35 parts by mass or less relative to a total of 100 parts by mass of carbon black and carbon nanotubes.

[0179] That is, the content of the carbon nanotubes in the positive electrode composition can be, for example, 1 to 90 parts by mass, 1 to 85 parts by mass, 1 to 80 parts by mass, 1 to 75 parts by mass, 1 to 70 parts by mass, 1 to 65 parts by mass, 1 to 60 parts by mass, 1 to 55 parts by mass, 1 to 50 parts by mass, 1 to 45 parts by mass, 1 to 40 parts by mass, 1 to 35 parts by mass, 5 to 90 parts by mass, 5 to 85 parts by mass, 5 to 80 parts by mass, 5 to 75 parts by mass, parts by weight, 5 to 70 parts by weight, 5 to 65 parts by weight, 5 to 60 parts by weight, 5 to 55 parts by weight, 5 to 50 parts by weight, 5 to 45 parts by weight, 5 to 40 parts by weight, 5 to 35 parts by weight, 10 to 90 parts by weight, 10 to 85 parts by weight, 10 to 80 parts by weight, 10 to 75 parts by weight, 10 to 70 parts by weight, 10 to 65 parts by weight, 10 to 60 parts by weight, 10 to 55 parts by weight, 10 to 50 parts by weight, 10 to 45 parts by weight, 10 to 40 parts by weight, 10-35 parts by mass, 15-90 parts by mass, 15-85 parts by mass, 15-80 parts by mass, 15-75 parts by mass, 15-70 parts by mass, 15-65 parts by mass, 15-60 parts by mass, 15-55 parts by mass, 15-50 parts by mass, 15-45 parts by mass, 15-40 parts by mass, 15-35 parts by mass, 20-90 parts by mass, 20-85 parts by mass, 20-80 parts by mass, 20-75 parts by mass, 20-70 parts by mass, 20-6 5 parts by mass, 20 to 60 parts by mass, 20 to 55 parts by mass, 20 to 50 parts by mass, 20 to 45 parts by mass, 20 to 40 parts by mass, 20 to 35 parts by mass, 25 to 90 parts by mass, 25 to 85 parts by mass, 25 to 80 parts by mass, 25 to 75 parts by mass, 25 to 70 parts by mass, 25 to 65 parts by mass, 25 to 60 parts by mass, 25 to 55 parts by mass, 25 to 50 parts by mass, 25 to 45 parts by mass, 25 to 40 parts by mass or 25 to 35 parts by mass.

[0180] Based on the total mass of the positive electrode composition, the total content of carbon nanotubes and carbon black in the positive electrode composition can be, for example, 0.1% by mass or more, and from the viewpoint of making the internal resistance smaller, and the discharge rate characteristics and cycle characteristics better, it can be 0.3% by mass or more, 0.5% by mass or more, 0.7% by mass or more, or 0.9% by mass or more. In addition, based on the total mass of the positive electrode composition, the total content of carbon nanotubes and carbon black in the positive electrode composition can be, for example, 5% by mass or less, and from the viewpoint of making the internal resistance smaller, and the discharge rate characteristics and cycle characteristics better, it can be 4% by mass or less, 3% by mass or less, 2% by mass or less, or 1.5% by mass or less.

[0181] That is, based on the total mass of the positive electrode composition, the total content of carbon nanotubes and carbon black in the positive electrode composition can be, for example, 0.1 to 5 mass%, 0.1 to 4 mass%, 0.1 to 3 mass%, 0.1 to 2 mass%, 0.1 to 1.5 mass%, 0.3 to 5 mass%, 0.3 to 4 mass%, 0.3 to 3 mass%, 0.3 to 2 mass%, 0.3 to 1.5 mass%, 0.5 to 5 mass%, 0.5 to 4 mass%, 0.5 to 3 mass%, 0.5 to 2 mass%, 0.5 to 1.5 mass%, 0.7 to 5 mass%, 0.7 to 4 mass%, 0.7 to 3 mass%, 0.7 to 2 mass%, 0.7 to 1.5 mass%, 0.9 to 5 mass%, 0.9 to 4 mass%, 0.9 to 3 mass%, 0.9 to 2 mass% or 0.9 to 1.5 mass%.

[0182] Based on the total mass of the positive electrode composition, the content of the binding material in the positive electrode composition can be, for example, 0.1% by mass or more, and from the viewpoint of making the internal resistance smaller, and the discharge rate characteristics and cycle characteristics are more excellent, it can be 0.5% by mass or more, 1% by mass or more, or 1.5% by mass or more. In addition, based on the total mass of the positive electrode composition, the content of the binding material in the positive electrode composition can be, for example, 10% by mass or less, and from the viewpoint of making the internal resistance smaller, and the discharge rate characteristics and cycle characteristics are more excellent, it can be 9% by mass or less, 8% by mass or less, 7% by mass or less, 6% by mass or less, 5% by mass or less, 4% by mass or less, or 3% by mass or less.

[0183] That is, based on the total mass of the positive electrode composition, the content of the binder in the positive electrode composition can be, for example, 0.1 to 10 mass%, 0.1 to 9 mass%, 0.1 to 8 mass%, 0.1 to 7 mass%, 0.1 to 6 mass%, 0.1 to 5 mass%, 0.1 to 4 mass%, 0.1 to 3 mass%, 0.5 to 10 mass%, 0.5 to 9 mass%, 0.5 to 8 mass%, 0.5 to 7 mass%, 0.5 to 6 mass%, 0. .5-5 mass %, 0.5-4 mass %, 0.5-3 mass %, 1-10 mass %, 1-9 mass %, 1-8 mass %, 1-7 mass %, 1-6 mass %, 1-5 mass %, 1-4 mass %, 1-3 mass %, 1.5-10 mass %, 1.5-9 mass %, 1.5-8 mass %, 1.5-7 mass %, 1.5-6 mass %, 1.5-5 mass %, 1.5-4 mass % or 1.5-3 mass %.

[0184] Based on the total mass of the positive electrode composition, the content of the active material in the positive electrode composition can be, for example, 90% by mass or more, and from the viewpoint of having better discharge rate characteristics and cycle characteristics, it can be 91% by mass or more, 92% by mass or more, 93% by mass or more, 94% by mass or more, or 95% by mass or more. In addition, based on the total mass of the positive electrode composition, the content of the active material in the positive electrode composition can be, for example, 99.5% by mass or less, and from the viewpoint of making the internal resistance smaller, it can be 99% by mass or less or 98% by mass or less.

[0185] That is, based on the total mass of the positive electrode composition, the content of the active material in the positive electrode composition can be, for example, 90-99.5 mass%, 90-99 mass%, 90-98 mass%, 91-99.5 mass%, 91-99 mass%, 91-98 mass%, 92-99.5 mass%, 92-99 mass%, 92-98 mass%, 93-99.5 mass%, 93-99 mass%, 93-98 mass%, 94-99.5 mass%, 94-99 mass%, 94-98 mass%, 95-99.5 mass%, 95-99 mass% or 95-98 mass%.

[0186] Based on the total mass of the positive electrode composition, the content of the dispersant in the positive electrode composition can be, for example, 0.05 mass % or more, 0.1 mass % or more, or 0.15 mass % or more. In addition, based on the total mass of the positive electrode composition, the content of the dispersant in the positive electrode composition can be, for example, 0.8 mass % or less, 0.5 mass % or less, or 0.2 mass % or less.

[0187] That is, based on the total mass of the positive electrode composition, the content of the dispersant in the positive electrode composition can be, for example, 0.05-0.8 mass%, 0.05-0.5 mass%, 0.05-0.2 mass%, 0.1-0.8 mass%, 0.1-0.5 mass%, 0.1-0.2 mass%, 0.15-0.8 mass%, 0.15-0.5 mass% or 0.15-0.2 mass%.

[0188] The positive electrode of the present embodiment can be produced by a production method including a positive electrode forming step of applying the positive electrode forming coating solution described above on a current collector to form a composite material layer composed of the positive electrode composition on the current collector.

[0189] The current collector is not particularly limited, and known current collectors can be used without particular limitation. As the current collector, for example, metal foil (metals such as gold, silver, copper, platinum, aluminum, iron, nickel, chromium, manganese, lead, tungsten, and titanium, and alloys with any of them as the main component) can be used. The current collector is usually provided in the form of foil, but is not limited thereto, and a perforated foil-shaped and mesh-shaped current collector can also be used.

[0190] The method for coating the positive electrode forming coating liquid on the collector is not particularly limited, and may be, for example, die coating, dip coating, roll coating, scraper coating, blade coating, spray coating, gravure coating, screen printing, or electrostatic coating.

[0191] The coating amount of the positive electrode forming coating liquid is not particularly limited and can be appropriately adjusted so that the thickness of the composite material layer falls within a desired range.

[0192] The composite material layer can be formed by removing at least a portion of the liquid medium from the coating film of the positive electrode forming coating liquid formed on the collector. The method for removing the liquid medium is not particularly limited, and for example, as a method for removing at least a portion of the liquid medium by vaporizing it by heating and / or reducing pressure, there can be cited a method of placing it for drying, a blower dryer, a hot air dryer, an infrared heater, a far infrared heater, etc.

[0193] The positive electrode manufacturing method of this embodiment may further include a pressurizing step of pressurizing the composite material layer and the current collector formed in the positive electrode forming step in a stacking direction. The pressurizing step can make the composite material layer and the current collector closely adhere to each other.

[0194] The pressing method in the pressing step is not particularly limited, and for example, it may be a method such as roll pressing, die pressing, or calendar pressing.

[0195] The thickness of the composite material layer in the positive electrode is not particularly limited, and can be, for example, 50 μm or more. From the perspective of high capacity of the battery, it is preferably 55 μm or more, more preferably 60 μm or more, and can be 65 μm or more or 70 μm or more. In addition, the thickness of the composite material layer in the positive electrode can be, for example, 150 μm or less. From the perspective of further improving the discharge rate characteristics, it is preferably 140 μm or less, more preferably 130 μm or less, and can be 120 μm or less or 110 μm or less.

[0196] That is, the thickness of the composite material layer in the positive electrode can be, for example, 50 to 150 μm, 50 to 140 μm, 50 to 130 μm, 50 to 120 μm, 50 to 110 μm, 55 to 150 μm, 55 to 140 μm, 55 to 130 μm, 55 to 120 μm, 55 to 110 μm, 60 to 150 μm, 60 to 140 μm, 60 to 130 μm, 60 to 120 μm, 60 to 110 μm, 65 to 150 μm, 65 to 140 μm, 65 to 130 μm, 65 to 120 μm, 65 to 110 μm, 70 to 150 μm, 70 to 140 μm, 70 to 130 μm, 70 to 120 μm or 70 to 110 μm.

[0197] The positive electrode of the present embodiment can be suitably used as a positive electrode of a battery, particularly a secondary battery (lithium ion secondary battery).

[0198] <Battery>

[0199] The battery of the present embodiment (preferably a secondary battery, more preferably a lithium ion secondary battery) has a positive electrode manufactured by the above-mentioned manufacturing method. In the battery of the present embodiment, the structure other than the positive electrode can be the same as that of a known battery. The manufacturing method of the battery in the present embodiment is not particularly limited, and can be the same method as the manufacturing method of a previously known battery except for using the positive electrode manufactured by the above-mentioned manufacturing method.

[0200] The battery of the present embodiment includes a positive electrode using the carbon black of the present embodiment, and therefore has a small internal resistance and is excellent in discharge rate characteristics and cycle characteristics.

[0201] The battery of this embodiment may include, for example, a positive electrode, a negative electrode, and a separator.

[0202] The separator is not particularly limited, and as a separator for lithium ion secondary batteries, known separators can be used without particular limitation. As the separator, for example, synthetic resins such as polyethylene and polypropylene can be cited. From the aspect of good retention of the electrolyte, the separator is preferably a porous film.

[0203] The battery of the present embodiment may include an electrode group in which a positive electrode and a negative electrode are stacked or wound with a separator interposed therebetween.

[0204] In the battery of this embodiment, the positive electrode, the negative electrode, and the separator may be immersed in the electrolyte solution.

[0205] The electrolyte is not particularly limited, and may be, for example, a non-aqueous electrolyte containing a lithium salt. Examples of the non-aqueous solvent in the non-aqueous electrolyte containing a lithium salt include ethylene carbonate, propylene carbonate, diethyl carbonate, dimethyl carbonate, ethyl methyl carbonate, and the like. In addition, examples of lithium salts that can be dissolved in a non-aqueous solvent include lithium hexafluorophosphate, lithium tetrafluoroborate, lithium trifluoromethanesulfonate, and the like. The battery of this embodiment may also use an ion-conducting polymer as an electrolyte.

[0206] The negative electrode in the battery of this embodiment may include, similarly to the negative electrode used in a common lithium ion secondary battery, a negative electrode composite material layer formed by coating a negative electrode composite material including a negative electrode active material and a binder on a negative electrode current collector, and a negative electrode current collector.

[0207] The use of the battery in this embodiment is not particularly limited, and it can be used in a wide range of fields, for example, in digital cameras, camcorders, portable audio players, portable LCD TVs and other portable AV devices, laptop computers, smart phones, mobile PCs and other portable information terminals, as well as portable game devices, power tools, electric bicycles, hybrid vehicles, electric vehicles, power storage systems, etc.

[0208] As mentioned above, although the preferred embodiment of the present invention was described, the present invention is not limited to the above-mentioned embodiment.

[0209] For example, one aspect of the present invention may be a method for manufacturing a coating liquid for forming a positive electrode, a method for manufacturing a positive electrode, or a method for manufacturing a battery, comprising the following steps: an image acquisition step, wherein a two-dimensional projection image of a primary aggregate of carbon black obtained by a transmission electron microscope is acquired; and a screening step, wherein, based on the two-dimensional projection image, the number of the first primary aggregate, the second primary aggregate, the third primary aggregate, and the fourth primary aggregate is respectively calculated, and the number ratio of the total number of the second primary aggregate and the third primary aggregate relative to the total number of the first primary aggregate, the second primary aggregate, the third primary aggregate, and the fourth primary aggregate is calculated, and the carbon black having the number ratio of 22% or more is screened. That is, the above-mentioned method for manufacturing a coating liquid for forming a positive electrode, the method for manufacturing a positive electrode, and the method for manufacturing a battery may also include the above-mentioned image acquisition step and the screening step.

[0210] Example

[0211] Hereinafter, the present invention will be described in more detail by way of examples, but the present invention is not limited to these examples.

[0212] (Manufacturing Example A1: Manufacture of Carbon Black (A1))

[0213] The nozzle installed in the upstream part of the cylindrical reactor (1m in diameter and 7m in length) was used to generate a force of 20Nm. 3 Acetylene (110° C.) was supplied as a raw material gas at a rate of 12 Nm / h from a nozzle arranged in a direction perpendicular to the raw material gas. 3 / h is supplied with oxygen (25°C) as a gas other than the raw material to produce carbon black, and is captured by a bag filter arranged at the downstream part of the reactor. Then, it is passed through a dry cyclone separator device and an iron removal magnet and recovered in a tank. It should be noted that the nozzle diameter is adjusted in such a way that the ejection speed of the raw material gas into the reactor becomes 5m / s and the ejection speed of the gas other than the raw material into the reactor becomes 8m / s.

[0214] (Manufacturing Examples A2 to A5: Manufacture of Carbon Blacks (A2) to (A5))

[0215] Carbon black was produced in the same manner as in Production Example A1 except that the supply amount and the ejection rate of oxygen (25° C.) were changed as shown in Table 1.

[0216] (Production Example X1: Production of Carbon Black (X1))

[0217] Carbon black was produced in the same manner as in Production Example A1 except that the supply amount and the ejection rate of oxygen (25° C.) were changed as shown in Table 1.

[0218] (Production Example X2: Production of Carbon Black (X2))

[0219] Carbon black was produced in the same manner as in Production Example A1 except that oxygen (25° C.) was supplied in parallel with the supply direction of the raw material gas.

[0220] [Table 1]

[0221] <![CDATA[Supply amount of oxygen (Nm 3 / h)]]> Oxygen ejection velocity (m / s) Production Example A1 12 8 Production Example A2 9.5 15 Production Example A3 8 15 Production Example A4 16 7 Production Example A5 8 10 Production Example X1 12 6 Manufacturing Example × 2 12 8 (Supply in parallel with the supply direction of raw material gas)

[0222] The carbon blacks obtained in Production Examples A1 to A5 and X1 to X2 were subjected to the following measurements.

[0223] (1) Specific surface area

[0224] The measurement was performed in accordance with the A method flow method (thermal conductivity measurement method) of JIS K6217-2:2017.

[0225] (2) DBP absorption

[0226] The DBP absorption amount refers to a value obtained by converting a value measured by the method described in Method B of JIS K6221 into a value equivalent to JIS K6217-4:2008 using the following formula (a).

[0227] DBP absorption = (A-10.974) / 0.7833...(a)

[0228] [In the formula, A represents the value of DBP absorption measured by the method described in Method B of JIS K6221.]

[0229] Next, the carbon black obtained in manufacturing examples A1 to A5 and X1 to X2 was dispersed in chloroform at an ultrasonic output power of 90 W for 10 minutes to loosen the secondary aggregates into primary aggregates, which were scooped onto a collodion film mesh and photographed using a transmission electron microscope at an observation magnification of 2000 times.

[0230] The image analysis software "Image-Pro Plus 6.2J (manufactured by Media Cybernetics)" was used to filter the obtained two-dimensional projection image (median filter. Option 7×7. Times: 3), and then the brightness range was manually extracted to match the primary aggregate. "Size (width)", "Size (length)", "Perimeter", and "Area" were selected from the measurement items, and the Feret diameter W (μm) in the short axis direction, the Feret diameter L (μm) in the long axis direction, the perimeter P (μm), and the projection area A (μm) of more than 100 randomly selected primary aggregates were measured. 2 ) was measured. The primary aggregate at one end of the image, the scale bar, and the background noise were removed. Based on formula (X), formula (Y), and formula (Z), the primary aggregate was divided into the first primary aggregate, the second primary aggregate, the third primary aggregate, and the fourth primary aggregate, and the number ratio of each was calculated. The results are shown in Table 2.

[0231] It should be noted that Figure 2 This is a diagram showing a two-dimensional projection image of primary aggregates of the carbon black (A3) of Production Example A3 obtained by a transmission electron microscope.

[0232] [Table 2]

[0233]

[0234] (Example 1)

[0235] <Manufacturing of coating solution for positive electrode formation>

[0236] Carbon black (A1) of manufacturing example A1, N-methyl-2-pyrrolidone (manufactured by Kanto Chemical Co., Ltd.) as a dispersion medium, and polyvinyl alcohol (manufactured by Denka, POVAL B05) as a dispersant were prepared. 10 parts by mass of carbon black (A1) and 1 part by mass of polyvinyl alcohol were added to 89 parts by mass of NMP, and stirred for 120 minutes using a planetary mixer (manufactured by PRIMIX, Hivis DisperMix 3D-5 model) to obtain a slurry (first dose).

[0237] Next, prepare a 6 nm average diameter and a BET specific surface area of ​​300 m 2 / g, average diameter / BET specific surface area of ​​0.02 carbon nanotubes (CNano, "Flotube6000"). To 95.0% by mass of NMP, 1.0% by mass of polyvinyl pyrrolidone (Daiichi Kogyo Seiyaku Co., Ltd., "PITZCOL K-90") and 4.0% by mass of carbon nanotubes were added, and a planetary mixer (PRIMIX, Hivis Disper Mix 3D-5) was used to stir for 120 minutes to prepare a slurry containing carbon nanotubes. The obtained slurry was added to a bead mill (MUGEN FLOWMGF2-ZA, Ashizawa Finetech Co., Ltd.) equipped with zirconia beads (diameter 0.5mm) and dispersed. After the dispersion treatment, the zirconia beads were removed by filtration to obtain a slurry (second dose).

[0238] Next, a polyvinylidene fluoride NMP solution (L#7208, manufactured by KUREHA Co., Ltd., third agent) as a binder and an active material having an average particle size D 50 10μm nickel·manganese·cobalt lithium (made by Beijing Dangsheng Company, "ME6E"), NMP as a dispersion medium. The first agent, the second agent, the third agent and the active material are mixed in a manner that the active material becomes 97.0 mass %, the carbon black becomes 0.7 mass %, the carbon nanotube becomes 0.3 mass %, and the binder becomes 2.0 mass % based on the total amount of solid components, and NMP is added until it becomes a viscosity that can be coated. A self-rotating revolution mixer (made by Thinky Company, Awatori Rentaro ARV-310) is used to mix until uniform, and a coating liquid for positive electrode formation is obtained.

[0239] <Manufacturing of positive electrode>

[0240] The coating liquid for positive electrode formation was applied to one side of an aluminum foil (UACJ) with a thickness of 15 μm using an applicator, and then placed in a dryer and pre-dried at 105°C for 1 hour to completely remove the NMP and form a composite material layer. Next, a roller press was used to pressurize the laminate at a linear pressure of 200 kg / cm to prepare the laminate in a manner such that the overall thickness was 80 μm. Next, the laminate was vacuum dried at 170°C for 3 hours to completely remove the residual water and obtain a positive electrode having a current collector and a composite material layer.

[0241] <Manufacturing of negative electrode>

[0242] Prepare pure water (manufactured by Kanto Chemical Co., Ltd.) as a solvent, artificial graphite (manufactured by Hitachi Chemical Co., Ltd., "MAG-D") as a negative electrode active material, styrene butadiene rubber (manufactured by Zeon Co., Ltd., "BM-400B", hereinafter referred to as SBR) as a binding material, and carboxymethyl cellulose (manufactured by Daicel Co., Ltd., "D2200", hereinafter referred to as CMC) as a dispersant.

[0243] Next, 1 part by mass of CMC and 97 parts by mass of artificial graphite were weighed and mixed, pure water was added to the mixture, and a self-rotating revolution mixer (made by Thinky, Awatori Rentaro ARV-310) was used to mix until uniform to obtain a mixture. Next, 2 parts by mass of SBR were weighed, added to the obtained mixture, and a self-rotating revolution mixer (made by Thinky, Awatori Rentaro ARV-310) was used to mix until uniform to obtain a negative electrode forming coating liquid. Next, the negative electrode forming coating liquid was applied to a copper foil (made by UACJ) with a thickness of 10 μm using an applicator, left to stand in a dryer, and pre-dried at 60 ° C for 1 hour. Next, a roller press was used to pressurize the laminate at a linear pressure of 50 kg / cm, and the laminate was prepared in a manner such that the overall thickness was 60 μm. Next, it was vacuum dried at 120 ° C for 3 hours to completely remove the residual moisture and obtain a negative electrode having a collector and a composite material layer.

[0244] (Battery manufacturing)

[0245] In a drying room where the dew point has been controlled to be below -50°C, the produced positive electrode is processed into 40×40mm, and the produced negative electrode is processed into 44×44mm, and then the aluminum tabs are welded to the positive electrode and the nickel tabs are welded to the negative electrode. The composite material layers of the positive electrode and the negative electrode are placed opposite each other in the center, and a polyolefin microporous membrane processed into 45×45mm is arranged between the positive electrode and the negative electrode. Next, the sheet-shaped outer packaging cut and processed into a 70×140mm square is folded in half along the center of the long side. Next, the outer packaging is configured in a manner that the aluminum tabs for the positive electrode and the nickel tabs for the negative electrode are exposed on the outside of the outer packaging, while the folded outer packaging is used to clamp the positive electrode / polyolefin microporous membrane / negative electrode stack. Next, a heat sealer was used to heat and weld the two sides of the outer package, including the side where the positive electrode aluminum tab and the negative electrode nickel tab were exposed. Then, 2 g of electrolyte (manufactured by Kishida Chemical Co., Ltd., containing ethylene carbonate / diethyl carbonate = 1 / 2 (volume ratio) and 1 M LiPF 6 After the electrolyte is fully infiltrated into the positive electrode, the negative electrode and the polyolefin microporous membrane, a vacuum heat sealer is used to reduce the internal pressure while the remaining side of the outer package is heated and welded to obtain a lithium ion secondary battery.

[0246] (Battery Evaluation)

[0247] [Internal resistance]

[0248] The produced battery was charged at 4.3V and 0.2C at a constant current and constant voltage at 25°C, and then discharged at a constant current of 0.2C to 3.0V. Then, 5 cycles of charge / discharge were performed under the same conditions, and then charged to a depth of charge of 50%. Then, impedance measurement was performed under the conditions of a frequency range of 10MHz to 0.001Hz and a vibration voltage of 5mV to measure the internal resistance. The results are shown in Table 3.

[0249] [Discharge rate characteristics (rate capacity retention rate)]

[0250] For the manufactured battery, after constant current constant voltage charging limited to 4.3V and 0.2C at 25°C, it was discharged to 3.0V at a constant current of 0.2C. Then, after recovery charging was performed again at a constant current constant voltage limited to 4.3V and 0.2C, it was discharged to 3.0V at a constant current of 0.2C, and the discharge capacity at this time was measured. Next, the recovery charging condition was set to charge at a constant current constant voltage limited to 4.3V and 0.2C. On the other hand, while the discharge current was changed stepwise to 0.5C, 1C, 2C, and 3C, recovery charging and discharging were repeated, and the discharge capacity relative to each discharge current was measured. As an indicator of the discharge rate characteristics of the battery, the capacity retention rate at 3C discharge relative to 0.2C discharge was calculated as the rate capacity retention rate. The results are shown in Table 3.

[0251] [Cycle characteristics (cycle capacity maintenance rate)]

[0252] The produced battery was charged at a constant current and constant voltage of 4.3V and 1C at 25°C, and then discharged to 3.0V at a constant current of 1C. The above charge and discharge were repeated for 500 cycles, and the discharge capacity in each cycle was measured. As an indicator of the cycle characteristics of the battery, the capacity retention rate after 500 cycles relative to the capacity retention rate after 1 cycle was calculated as the cycle capacity retention rate. The results are shown in Table 3.

[0253] <Example 2>

[0254] A battery was produced and evaluated in the same manner as in Example 1 except that the carbon black (A1) in Example 1 was changed to the carbon black (A2).

[0255] <Example 3>

[0256] In addition to changing the carbon nanotubes of Example 1 to have an average diameter of 9 nm and a BET specific surface area of ​​250 m 2 A battery was prepared and evaluated in the same manner as in Example 1 except that carbon nanotubes having an average diameter / BET specific surface area of ​​0.036 (manufactured by CNano Corporation, "Flotube 7000") were used.

[0257] <Example 4>

[0258] A battery was produced and evaluated in the same manner as in Example 1 except that the carbon black (A1) in Example 1 was changed to the carbon black (A5).

[0259] <Example 5>

[0260] A battery was produced and evaluated in the same manner as in Example 1 except that the carbon black (A1) in Example 1 was changed to the carbon black (A3).

[0261] <Example 6>

[0262] In addition to changing the carbon nanotubes of Example 1 to have an average diameter of 12 nm and a BET specific surface area of ​​180 m 2 A battery was prepared and evaluated in the same manner as in Example 1 except that carbon nanotubes having an average diameter / BET specific surface area of ​​0.067 (manufactured by CNano Corporation, "Flotube 9000") were used.

[0263] <Example 7>

[0264] A battery was manufactured and evaluated in the same manner as in Example 1, except that the amounts of the first and second agents were changed so that the content of carbon black in the positive electrode forming coating liquid became 0.5 mass % (based on the total mass of the solid components) and the content of carbon nanotubes in the positive electrode forming coating liquid became 0.5 mass % (based on the total mass of the solid components).

[0265] <Example 8>

[0266] A battery was manufactured and evaluated in the same manner as in Example 1, except that the amounts of the first and second agents were changed so that the content of carbon black in the positive electrode forming coating liquid became 0.9 mass % (based on the total mass of the solid components) and the content of carbon nanotubes in the positive electrode forming coating liquid became 0.1 mass % (based on the total mass of the solid components).

[0267] <Example 9>

[0268] A battery was produced and evaluated in the same manner as in Example 1 except that the carbon black (A1) in Example 1 was changed to the carbon black (A4).

[0269] <Example 10>

[0270] The active material of Example 1 was changed to have an average particle size D 50 The battery was manufactured and evaluated in the same manner as in Example 1 except that the amount of the first and second agents was changed so that the content of carbon black in the positive electrode forming coating liquid became 0.9 mass % (based on the total mass of the solid components) and the content of carbon nanotubes in the positive electrode forming coating liquid became 0.1 mass % (based on the total mass of the solid components).

[0271] <Example 11>

[0272] The carbon black (A1) in Example 1 was replaced with carbon black (A2), and the carbon nanotubes were replaced with carbon black (A2) having an average diameter of 9 nm and a BET specific surface area of ​​250 m 2 / g, carbon nanotubes with an average diameter / BET specific surface area of ​​0.036 (manufactured by CNano, "Flotube7000"), and the amounts of the first and second agents were changed so that the content of carbon black in the positive electrode forming coating liquid became 0.1 mass % (based on the total mass of the solid components) and the content of carbon nanotubes in the positive electrode forming coating liquid became 0.9 mass % (based on the total mass of the solid components). Except for this, the battery was manufactured and evaluated by the same method as in Example 1.

[0273] <Comparative Example 1>

[0274] The carbon black (A1) in Example 1 was changed to carbon black (A3), carbon nanotubes were not used, and the amount of the first agent was changed so that the content of carbon black in the coating liquid for forming the positive electrode became 1 mass % (based on the total mass of the solid components). Except for this, the battery was manufactured and evaluated using the same method as Example 1.

[0275] <Comparative Example 2>

[0276] The carbon nanotubes of Example 1 were changed to have an average diameter of 9 nm and a BET specific surface area of ​​250 m 2 / g, and carbon nanotubes with an average diameter / BET specific surface area of ​​0.036 (manufactured by CNano, "Flotube7000"), without using carbon black, and changing the amount of the second agent so that the content of carbon nanotubes in the positive electrode forming coating liquid becomes 1 mass % (based on the total mass of the solid component). Except for this, the battery was manufactured and evaluated by the same method as in Example 1.

[0277] <Comparative Example 3>

[0278] In addition to changing the carbon nanotubes of Example 1 to have an average diameter of 32 nm and a BET specific surface area of ​​110 m 2 A battery was prepared and evaluated in the same manner as in Example 1 except that carbon nanotubes (manufactured by Tokyo Chemical Industry Co., Ltd., “MWNT”) having an average diameter / BET specific surface area of ​​0.29 were used.

[0279] <Comparative Example 4>

[0280] The carbon nanotubes of Example 1 were changed to have an average diameter of 2.5 nm and a BET specific surface area of ​​740 m 2 / g, carbon nanotubes with an average diameter / BET specific surface area of ​​0.003 (manufactured by Sigma-Aldrich, "Signis FW100"), and the amounts of the first and second agents were changed so that the content of carbon black in the positive electrode forming coating liquid became 0.9 mass % (based on the total mass of the solid components) and the content of carbon nanotubes in the positive electrode forming coating liquid became 0.1 mass % (based on the total mass of the solid components). Except for this, the battery was prepared and evaluated by the same method as in Example 1.

[0281] <Comparative Example 5>

[0282] A battery was produced and evaluated in the same manner as in Example 1 except that the carbon black (A1) in Example 1 was changed to the carbon black (X1).

[0283] <Comparative Example 6>

[0284] A battery was produced and evaluated in the same manner as in Example 1 except that the carbon black (A1) in Example 1 was changed to the carbon black (X2).

[0285] [Table 3]

[0286]

Claims

1. A positive electrode composition comprising carbon black, carbon nanotubes, a binding material, and an active material, The carbon nanotubes have an average diameter of 5 to 15 nm. When the carbon black is divided into a first primary aggregate, a second primary aggregate, a third primary aggregate, and a fourth primary aggregate, the total number of the second primary aggregate and the third primary aggregate is 22% or more relative to the total number of the first primary aggregate, the second primary aggregate, the third primary aggregate, and the fourth primary aggregate, The value of X of the first primary aggregate obtained by the following formula (X) is greater than 1.7, The X value of the second primary aggregate is 1.7 or less, and the Y value obtained by the following formula (Y) is 1.2 or less, The X value of the third primary aggregate is 1.7 or less, the Y value is greater than 1.2, and the Z value calculated by the following formula (Z) is 2.0 or less, The X value of the fourth primary aggregate is less than 1.7, the Y value is greater than 1.2, and the Z value is greater than 2.0, X=L / W(X) Y=P 2 / 4πA(Y) Z=(L×W) / A(Z) Wherein, in the two-dimensional projection image of the primary aggregate obtained by transmission electron microscopy, the Fret diameter in the short axis direction of the primary aggregate is W (μm), the Fret diameter in the long axis direction of the primary aggregate is L (μm), the perimeter of the primary aggregate is P (μm), and the projected area of ​​the primary aggregate is A (μm 2 ).

2. The positive electrode composition according to claim 1, wherein The ratio of the average diameter of the carbon nanotubes to the BET specific surface area (average diameter / BET specific surface area) is 0.01 to 0.1 nm / (m 2 / g). 3 . A positive electrode comprising a composite material layer formed from the positive electrode composition according to claim 1 .

4. A battery comprising the positive electrode according to claim 3.

5. A method for producing a coating liquid for forming a positive electrode, comprising: A mixing step of mixing carbon black with a first liquid medium to obtain a first agent containing the carbon black and the first liquid medium; and a coating liquid forming step of mixing the first agent, the second agent containing carbon nanotubes and a second liquid medium, the third agent containing a binder and a third liquid medium, and an active material to form a positive electrode forming coating liquid, The carbon nanotubes have an average diameter of 5 to 15 nm. When the carbon black is divided into a first primary aggregate, a second primary aggregate, a third primary aggregate, and a fourth primary aggregate, the total number of the second primary aggregate and the third primary aggregate is 22% or more relative to the total number of the first primary aggregate, the second primary aggregate, the third primary aggregate, and the fourth primary aggregate, The value of X of the first primary aggregate obtained by the following formula (X) is greater than 1.7, The X value of the second primary aggregate is 1.7 or less, and the Y value obtained by the following formula (Y) is 1.2 or less, The X value of the third primary aggregate is 1.7 or less, the Y value is greater than 1.2, and the Z value calculated by the following formula (Z) is 2.0 or less, The X value of the fourth primary aggregate is less than 1.7, the Y value is greater than 1.2, and the Z value is greater than 2.0, X=L / W(X) Y=P 2 / 4πA(Y) Z=(L×W) / A(Z) Wherein, in the two-dimensional projection image of the primary aggregate obtained by transmission electron microscopy, the Fret diameter in the short axis direction of the primary aggregate is W (μm), the Fret diameter in the long axis direction of the primary aggregate is L (μm), the perimeter of the primary aggregate is P (μm), and the projected area of ​​the primary aggregate is A (μm 2 ).

6. A method for manufacturing a positive electrode, comprising the following positive electrode forming step: applying a coating liquid for forming a positive electrode manufactured by the manufacturing method described in claim 5 onto a current collector, forming a composite material layer on the current collector formed by a positive electrode composition containing the carbon black, the carbon nanotubes, the binding material and the active material, to obtain a positive electrode comprising the current collector and the composite material layer.

7. A method for manufacturing a battery, comprising the following positive electrode forming step: applying a coating liquid for forming a positive electrode manufactured by the manufacturing method described in claim 5 onto a current collector, forming a composite material layer on the current collector formed by a positive electrode composition containing the carbon black, the carbon nanotubes, the binding material and the active material, to obtain a positive electrode comprising the current collector and the composite material layer.